Positive electrode active material, secondary battery, electronic device, and vehicle

By adding a specific proportion of nickel and cobalt to the positive electrode active substance of the lithium-ion secondary battery and adding specific elements to the surface, the lithium-ion secondary battery has been solved in terms of discharge capacity, cycle characteristics, reliability, safety and cost. The shortcomings achieve higher battery performance and safety.

CN119404337APending Publication Date: 2025-02-07SEMICON ENERGY LAB CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380047366.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-21
Filing Date
2023-06-09
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries still have room for improvement in discharge capacity, cycle characteristics, reliability, safety or cost.

Method used

A positive electrode active substance containing cobalt, nickel, oxygen and added elements is used. Specifically, the proportion of nickel in the sum of cobalt and nickel is between 0.025 and 0.215, and the added element concentration of the surface layer is higher than that of the internal added element concentration. , and the added elements are one or more of magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

Benefits of technology

It effectively suppresses the decrease in discharge capacity during the charge and discharge cycle, improves the stability of the crystal structure, enhances the thermal stability and safety of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404337A_ABST
    Figure CN119404337A_ABST
Patent Text Reader

Abstract

Provided is a positive electrode active material in which a decrease in discharge capacity during a charge / discharge cycle is suppressed. The positive electrode active material contains cobalt, nickel, and oxygen, and the ratio of nickel to the sum of cobalt and nickel (Ni / (Co + Ni)) is more than 0.175 but 0.215 or less. The positive electrode active material has diffraction peaks at at least two of 2 [theta] = 18.526 + / -0.1 DEG, 2 [theta] = 37.391 + / -0.1 DEG, 2 [theta] = 37.628 + / -0.1 DEG, 2 [theta] = 39.015 + / -0.1 DEG, 2 [theta] = 44.947 + / -0.1 DEG, 2 [theta] = 49.029 + / -0.1 DEG, and 2 [theta] = 58.857 + / -0.1 DEG when analyzed by X-ray powder diffraction using a CuK [alpha] 1 line in a state of being charged to 4.5 V (vs. Li / Li +).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to an article, method or manufacturing method. In addition, the present invention relates to a process, machine, product or composition of matter. One embodiment of the present invention relates to a storage device including a secondary battery, a semiconductor device, a display device, a light-emitting device, a lighting device, an electronic device or a manufacturing method thereof.

[0002] Note that in this specification, electronic equipment refers to any device having a power storage device. An electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all electronic equipment. Background Art

[0003] In recent years, the development of various power storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries and all-solid-state batteries has become increasingly popular. In particular, with the development of the semiconductor industry, the demand for high-output, high-capacity lithium-ion secondary batteries has increased dramatically, and as a rechargeable energy supply source, it has become a necessity in the modern information society.

[0004] In particular, secondary batteries for portable electronic devices are required to have a large discharge capacity per unit weight and high cycle characteristics. In order to meet these requirements, improvements are being actively made to the positive electrode active material contained in the positive electrode of the secondary battery (for example, Patent Documents 1 to 3). In addition, research on the crystal structure of the positive electrode active material has been conducted (Non-Patent Documents 1 to 5).

[0005] In addition, X-ray diffraction (XRD: X-ray Diffraction) is one of the methods for analyzing the crystal structure of the positive electrode active material. XRD data can be analyzed by using ICSD (Inorganic Crystal Structure Database) introduced in non-patent document 6. For example, ICSD can be used to refer to the lattice constant of lithium cobalt oxide described in non-patent document 7. In addition, analysis using the Rietveld method can use, for example, the analysis program RIETAN-FP (refer to non-patent document 8).

[0006] As image processing software, for example, ImageJ is known (Non-Patent Documents 9 to 11). By using this software, for example, the shape of the positive electrode active material can be analyzed.

[0007] Nanobeam electron diffraction is also effective in identifying the crystal structure of the positive electrode active material, especially the crystal structure of the surface layer. For example, the analysis program ReciPro (Non-Patent Document 12) can be used for analyzing the electron diffraction pattern.

[0008] Fluorides such as fluorite (calcium fluoride) have been used as fluxes in ironmaking and the like since ancient times, and their physical properties have been studied (Non-Patent Document 13).

[0009] Various studies and developments have also been conducted on the reliability and safety of lithium-ion secondary batteries. For example, Non-Patent Document 14 describes the thermal stability of positive electrode active materials and electrolyte solutions. [Prior technical literature] [Patent Document]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 2019-179758 [Patent Document 2] WO2020 / 026078 Pamphlet [Patent Document 3] Japanese Patent Application Publication No. 2020-140954 [Non-patent literature]

[0011] [Non-patent document 1] Toyoki Okumura et al, "Correlation of lithium iondistribution and X-ray absorption near-edge structure in O3-and O2-lithiumcobalt oxides from first-principle calculation", Journal of MaterialsChemistry, 2012, 22, p.17340-17348 [Non-patent document 2] Motohashi, T. et al., "Electronic phase diagram of the layered cobalt oxide system Li x CoO2(0.0≤x≤1.0)”, Physical Review B, 80(16); 165114 [Non-patent document 3] Zhaohui Chen et al., “Staging Phase Transitions in Li x CoO2", Journal of The Electrochemical Society, 2002, 149(12)A1604-A1609 [Non-patent document 4] GG Amucci et al., "CoO2, The End Member of the Lix CoO2 Solid Solution" J. Electrochem. Soc. 143 (3) 1114 (1996). [Non-patent document 5] Atsushi Ueda and Tsutomu Ohzuku, “Solid-State Redox Reactions of LiNi 1 / 2 Co 1 / 2 O2(R3m) for 4Volt Secondary Lithium Cells”Journal ofThe Electrochemical Society, Vol.141, No.8, August1994. [Non-patent document 6] Belsky, A. et al., "New developments in the InorganicCrystal Structure Database (ICSD): accessibility in support of materials research and design", Acta Cryst., (2002) B58 364-369. [Non-patent document 7] Akimoto, J.; Gotoh, Y.; Oosawa, Y. "Synthesis and structurerefinement of Li Co O2 single crystals" Journal of Solid State Chemistry (1998) 141, p. 298-302. [Non-patent document 8] F. Izumi and K. Momma, Solid State Phenom., 130, 15-20 (2007) [Non-patent document 9] Rasband, WS, ImageJ, USNational Institutes of Health, Bethesda, Maryland, USA, http: / / rsb.info.nih.gov / ij / , 1997-2012. [Non-patent document 10] Schneider, CA, Rasband, WS, Eliceiri, KW "NIH Image to ImageJ: 25 years of image analysis". Nature Methods 9, 671-675, 2012. [Non-patent document 11] Abramoff, MD, Magelhaes, PJ, Ram, SJ "Image Processing with ImageJ". Biophotonics International, volume 11, issue 7, pp. 36-42, 2004. [Non-patent document 12] Seto, Y. & Ohtsuka, M. "ReciPro: free and open-source multipurpose crystallographic software integrating a crystal model database and viewer, diffraction and microscopy simulators, and diffraction data analysis tools" (2022). J.Appl.Cryst.55. [Non-patent document 13] WE Counts, R. Roy, and EFOsborn, "Fluoride ModelSystems: II, The Binary Systems CaF2-BeF2, MgF2-BeF2, and LiF-MgF2", Journal of the American Ceramic Society, 36[1] 12-17 (1953). [Non-patent document 14] Kitano Shinya et al., GS Yuasa Technical Report Vol. 2 No. 2, December 2015, pp. 18-24. Summary of the invention Technical problem to be solved by the invention

[0012] Lithium-ion secondary batteries still have room for improvement in various aspects such as discharge capacity, cycle characteristics, reliability, safety, and cost.

[0013] Therefore, as positive electrode active materials used in the above-mentioned lithium ion secondary batteries, materials that can improve discharge capacity, cycle characteristics, reliability, safety, cost, and other issues when used in secondary batteries are also required.

[0014] One of the purposes of one embodiment of the present invention is to provide a positive electrode active material or a composite oxide, which can be used in a lithium ion secondary battery and the discharge capacity decrease of the charge and discharge cycle is suppressed. In addition, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material or a composite oxide that is not easy to cause crystal structure collapse even if it is repeatedly charged and discharged. In addition, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material or a composite oxide with a large discharge capacity. In addition, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material or a composite oxide with a high yield. In addition, one of the purposes of one embodiment of the present invention is to provide a positive electrode active material or a composite oxide with high thermal stability. In addition, one of the purposes of one embodiment of the present invention is to provide a secondary battery with high safety or reliability.

[0015] Another object of one embodiment of the present invention is to provide a power storage device or a method for manufacturing the same.

[0016] Note that the description of these objects does not prevent the existence of other objects. Note that one embodiment of the present invention does not necessarily achieve all of the above objects. Note that objects other than the above objects can be extracted from the description of the specification, drawings, and claims. Solutions to technical problems

[0017] One embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and an additive element, wherein the ratio of nickel to the sum of cobalt and nickel, Ni / (Co+Ni), is greater than 0.025 and is less than 0.215, the positive electrode active material includes a surface portion and an interior portion, the concentration of the additive element in the surface portion is higher than the concentration of the additive element in the interior portion, and the additive element is one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

[0018] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and added elements, wherein the ratio of nickel to the sum of cobalt and nickel Ni / (Co+Ni) is greater than 0.175 and less than 0.215, the positive electrode active material includes a surface portion and an interior portion, the average detected amount of the added elements in the surface portion is higher than the average detected amount of the added elements in the interior, and the added elements are one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

[0019] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.5V (vs. Li / Li +) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.526±0.1°, 2θ=37.391±0.1°, 2θ=37.628±0.1°, 2θ=39.015±0.1°, 2θ=44.947±0.1°, 2θ=49.029±0.1° and 2θ=58.857±0.1°.

[0020] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.351±0.1°, 2θ=37.412±0.1°, 2θ=38.974±0.1°, 2θ=44.865±0.1°, 2θ=48.864±0.1° and 2θ=58.621±0.1°.

[0021] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.7V (vs. Li / Li + ) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.382±0.1°, 2θ=37.391±0.1° and 2θ=44.886±0.1°.

[0022] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and an additive element, wherein the additive element is magnesium and fluorine, the ratio of nickel to the sum of cobalt and nickel (Ni / (Co+Ni)) is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.5V (vs.Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.516±0.1°, 2θ=37.391±0.1°, 2θ=37.586±0.1°, 2θ=38.995±0.1°, 2θ=44.947±0.1°, 2θ=49.039±0.1° and 2θ=58.898±0.1°.

[0023] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and an additive element, wherein the additive element is magnesium and fluorine, the ratio of nickel to the sum of cobalt and nickel (Ni / (Co+Ni)) is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.6V (vs.Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.608±0.1°, 2θ=37.381±0.1°, 2θ=37.792±0.1°, 2θ=39.015±0.1°, 2θ=44.999±0.1°, 2θ=49.101±0.1° and 2θ=58.991±0.1°.

[0024] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.403±0.1°, 2θ=37.412±0.1°, 2θ=38.985±0.1°, 2θ=44.875±0.1°, 2θ=48.916±0.1° and 2θ=58.662±0.1°.

[0025] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.608±0.1°, 2θ=37.381±0.1°, 2θ=37.854±0.1°, 2θ=38.995±0.1°, 2θ=45.009±0.1° and 2θ=59.073±0.1°.

[0026] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.215, and the positive electrode active material is charged to 4.7V (vs. Li / Li +) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.413±0.1°, 2θ=36.774±0.1°, 2θ=37.412±0.1° and 2θ=44.958±0.1°.

[0027] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and an additive element, wherein the proportion of nickel in the sum of cobalt and nickel, Ni / (Co+Ni), is greater than 0.075 and less than 0.125, and the positive electrode active material includes a surface portion and an interior portion, the average detected amount of the additive element in the surface portion is higher than the average detected amount of the additive element in the interior, and the additive element is one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

[0028] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.075 and less than 0.125, and the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.434±0.1°, 2θ=37.401±0.1°, 2θ=39.005±0.1°, 2θ=44.896±0.1°, 2θ=48.957±0.1° and 2θ=58.744±0.1°.

[0029] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.075 and less than 0.125, and the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.567±0.1°, 2θ=37.381±0.1°, 2θ=39.005±0.1° and 2θ=44.978±0.1°.

[0030] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and an additive element, wherein the additive element is magnesium and fluorine, the ratio of nickel to the sum of cobalt and nickel (Ni / (Co+Ni)) is greater than 0.075 and less than 0.125, and the positive electrode active material is charged to 4.5V (vs.Li / Li +) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.537±0.1°, 2θ=37.391±0.1°, 2θ=37.658±0.1°, 2θ=39.005±0.1°, 2θ=44.958±0.1°, 2θ=49.039±0.1° and 2θ=58.898±0.1°.

[0031] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and an additive element, wherein the additive element is magnesium and fluorine, the ratio of nickel to the sum of cobalt and nickel (Ni / (Co+Ni)) is greater than 0.075 and less than 0.125, and the positive electrode active material is charged to 4.6V (vs.Li / Li + ) in a state of being prepared by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.547±0.1°, 2θ=37.381±0.1°, 2θ=38.985±0.1°, 2θ=44.978±0.1°, 2θ=49.101±0.1° and 2θ=59.073±0.1°.

[0032] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel, oxygen and added elements, wherein the proportion of nickel in the sum of cobalt and nickel Ni / (Co+Ni) is greater than 0.025 and less than 0.075, the positive electrode active material includes a surface portion and an interior portion, the average detected amount of the added element in the surface portion is higher than the average detected amount of the added element in the interior, and the added element is one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

[0033] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.025 and less than 0.075, and the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.567±0.1°, 2θ=37.381±0.1°, 2θ=37.710±0.1°, 2θ=38.985±0.1°, 2θ=44.968±0.1°, 2θ=49.070±0.1° and 2θ=58.980±0.1°.

[0034] Another embodiment of the present invention is a positive electrode active material comprising cobalt, nickel and oxygen, wherein the ratio of nickel to the sum of cobalt and nickel is greater than 0.025 and less than 0.075, and the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.866±0.1°, 2θ=37.319±0.1°, 2θ=38.337±0.1°, 2θ=38.985±0.1°, 2θ=45.143±0.1°, 2θ=49.368±0.1° and 2θ=59.515±0.1°.

[0035] Another embodiment of the present invention is a secondary battery including the above-mentioned positive electrode active material.

[0036] Another embodiment of the present invention is an electronic device including the secondary battery.

[0037] Another aspect of the present invention is a vehicle including the above-mentioned secondary battery. Effects of the Invention

[0038] According to one embodiment of the present invention, a positive electrode active material or a composite oxide can be provided, which can be used in a lithium-ion secondary battery and the discharge capacity decrease of the charge and discharge cycle is suppressed. In addition, according to one embodiment of the present invention, a positive electrode active material or a composite oxide that is not easy to cause crystal structure collapse even if it is repeatedly charged and discharged can be provided. In addition, according to one embodiment of the present invention, a positive electrode active material or a composite oxide with a large discharge capacity can be provided. In addition, according to one embodiment of the present invention, a positive electrode active material or a composite oxide with a high production rate can be provided. In addition, according to one embodiment of the present invention, a positive electrode active material or a composite oxide with high thermal stability can be provided. In addition, according to one embodiment of the present invention, a secondary battery with high safety or reliability can be provided.

[0039] Furthermore, according to one embodiment of the present invention, a power storage device or a method for manufacturing the same can be provided.

[0040] Note that the description of these effects does not prevent the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of the above effects. Note that effects other than the above can be known and extracted from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1A and Figure 1B It is a cross-sectional view of the positive electrode active material. Figure 2This is an example of a TEM image in which the orientation of the crystals is roughly uniform. Figure 3A This is an example of a STEM image where the orientation of the crystals is roughly uniform. Figure 3B is the FFT pattern of the rock salt crystal RS region, Figure 3C is the FFT pattern of the region of layered rock salt type crystal LRS. FIG. 4A to FIG. 4C It is a diagram for explaining a method for producing a positive electrode active material. Figure 5A and Figure 5B It is a cross-sectional view of the positive electrode active material. Figure 6 It is a diagram showing the appearance of a secondary battery. 7A to 7C It is a diagram for explaining a method for manufacturing a secondary battery. FIG. 8A to FIG. 8H It is a diagram for explaining an example of an electronic device. 9A to 9D It is a diagram for explaining an example of an electronic device. FIG. 10A to FIG. 10C It is a diagram for explaining an example of an electronic device. FIG. 11A to FIG. 11C It is a diagram for explaining an example of a vehicle. Fig.12 This is the XRD pattern of the positive electrode active material. Fig.13A and Fig. 13B This is the XRD pattern of the positive electrode active material. Fig.14A and Fig. 14B This is the XRD pattern of the positive electrode active material. Fig.15 This is the XRD pattern of the positive electrode active material. Fig.16A and Fig. 16B This is the XRD pattern of the positive electrode active material. Fig.17A and Fig. 17B This is the XRD pattern of the positive electrode active material. Fig.18 This is the XRD pattern of the positive electrode active material. Fig.19A and Fig.19B This is the XRD pattern of the positive electrode active material. Fig. 20A and Fig. 20B This is the XRD pattern of the positive electrode active material. Fig.21 This is the XRD pattern of the positive electrode active material. Fig.22A and Fig. 22BThis is the XRD pattern of the positive electrode active material. Fig.23A and Fig. 23B This is the XRD pattern of the positive electrode active material. Fig.24 This is the XRD pattern of the positive electrode active material. Fig.25A and Fig.25B This is the XRD pattern of the positive electrode active material. Fig.26A and Fig.26B This is the XRD pattern of the positive electrode active material. Fig. 27 This is the XRD pattern of the positive electrode active material. Fig.28A and Fig.28B This is the XRD pattern of the positive electrode active material. Fig.29A and Fig.29B This is the XRD pattern of the positive electrode active material. Fig.30 This is the XRD pattern of the positive electrode active material. Fig.31A and Fig.31B This is the XRD pattern of the positive electrode active material. Fig.32A and Fig.32B This is the XRD pattern of the positive electrode active material. Fig.33 This is the XRD pattern of the positive electrode active material. Fig.34A and Fig.34B This is the XRD pattern of the positive electrode active material. Fig.35A and Fig.35B This is the XRD pattern of the positive electrode active material. Fig.36 This is the XRD pattern of the positive electrode active material. Fig.37A and Fig.37B This is the XRD pattern of the positive electrode active material. Fig.38A and Fig.38B This is the XRD pattern of the positive electrode active material. Modes for Carrying Out the Invention

[0042] Hereinafter, examples of embodiments of the present invention will be described with reference to the drawings, etc. However, the present invention should not be construed as being limited to the following examples of embodiments. The embodiments of the invention may be changed within the scope of the spirit of the present invention.

[0043] In this specification and the like, the space group is represented by the Shortnotation of the international symbol (or Hermann-Mauguin notation). In addition, Miller indices are used to represent crystal planes and crystal orientations. In crystallography, a bar is attached to a number to represent the space group, crystal plane, and crystal orientation. However, in this specification and the like, due to format limitations, a - (negative sign) may be attached in front of the number instead of attaching a bar to the number. In addition, "[]" represents an individual orientation showing the orientation within the crystal, "<>" represents a set orientation showing all equivalent orientations, "()" represents an individual face of the crystal plane, and "{}" represents a set of faces with equivalent symmetry. In general, for ease of understanding the structure, the trigonal system represented by the space group R-3m is represented by a composite hexagonal lattice of a hexagonal lattice. In this specification and the like, unless otherwise specified, the space group R-3m is represented by a composite hexagonal lattice. Sometimes, in addition to (hkl), (hkil) is also used as Miller indices. Here, i is - (h + k). In this specification and the like, unless otherwise specified, the crystal planes of the space group R-3m and the like are represented by a composite hexagonal lattice.

[0044] In addition, in this specification and the like, the particles are not limited to spherical (the cross-sectional shape is circular), and the cross-sectional shape of each particle can also be elliptical, rectangular, trapezoidal, triangular, a quadrilateral with rounded corners, an asymmetric shape, etc., and each particle can also be amorphous.

[0045] Furthermore, the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the lithium that can be inserted and removed in the positive electrode active material is removed. For example, the theoretical capacity of LiCoO2 is 274 mAh / g, the theoretical capacity of LiNiO2 is 274 mAh / g, and the theoretical capacity of LiMn2O4 is 148 mAh / g.

[0046] In addition, for x in the compositional formula, for example, in Li x MO2, x represents how much lithium remains in the positive electrode active material compared to the theoretical capacity. Note that M represents a transition metal, and when there is no special specification in this specification and the like, M is the sum of cobalt and nickel. In the positive electrode active material of a secondary battery, x = (theoretical capacity - charging capacity) / theoretical capacity. For example, when a secondary battery using LiMO2 as the positive electrode active material is charged to 219.2 mAh / g, it can be said to be Li 0.2 MO2, or it can be said that x = 0.2. A small x in Li x MO2, for example, means 0.1 < x ≤ 0.24. In addition, the degree of lithium detached from the positive electrode active material relative to the theoretical capacity is sometimes referred to as the depth of charge. In this specification and the like, the depth of charge = 1 - x.

[0047] When lithium cobalt nickel oxide roughly satisfies the stoichiometric ratio, it is LiMO2 and the occupancy rate of Li at the lithium position is x=1. In addition, a secondary battery at the end of discharge can also be said to be LiMO2 and x=1. Here, "end of discharge" refers to, for example, a state where the current is 100mA / g and the voltage is below 2.5V (to the electrode lithium). In a lithium-ion secondary battery, the voltage drops sharply when the occupancy rate of lithium at the lithium position is x=1 and other lithium cannot be embedded. It can be said that the discharge is ended at this time. In general, the discharge voltage of a lithium-ion secondary battery using LiMO2 drops sharply before reaching 2.5V, so it is assumed that the discharge is ended under the above conditions. In addition, when the positive electrode at the end of discharge is analyzed using XRD, etc., it can be confirmed that it has a general LiMO2 crystal structure.

[0048] To calculate Li x The charge capacity and / or discharge capacity of x in MO2 is preferably measured under conditions without or with little effect of decomposition by short circuit and / or electrolyte, etc. For example, data of a secondary battery that has undergone a rapid capacity change that is considered a short circuit cannot be used to calculate x.

[0049] In addition, the space group of the crystal structure is identified by XRD, electron diffraction, neutron diffraction, etc. Therefore, in this specification, etc., belonging to a certain space group or a space group can also be said to be identified as a certain space group.

[0050] In addition, when the configuration of anions is roughly close to the cubic closest packing, it can be regarded as the cubic closest packing. The cubic closest packing anion configuration refers to the following state: the anions of the second layer are configured on the gaps of the anions filled in the first layer, and the anions of the third layer are configured just on the gaps of the anions of the second layer but not just on the anions of the first layer. Therefore, the anions may not be strictly cubic lattices. At the same time, in fact, the crystals all have defects, so the analysis results may not be based on theory. For example, spots may also appear in FFT (Fast Fourier Transform: Fast Fourier Transform) patterns of electron diffraction patterns or TEM (Transmission Electron Microscope: Transmission Electron Microscope) images, etc., at positions slightly different from the theoretical positions. For example, when the difference in orientation from the theoretical position is less than 5 degrees or less than 2.5 degrees, it can be said that there is a cubic closest packing structure.

[0051] The distribution of an element refers to a region where the element is continuously detected in a range that is not considered as noise in a continuous analysis method. The region where the element is continuously detected in a range that is not considered as noise can also be said to be a region where the element is detected each time when multiple analyses are performed.

[0052] In addition, the positive electrode active material to which the additional element is added is sometimes recorded as a composite oxide, a positive electrode material, a positive electrode material for a secondary battery, etc. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably comprises a compound. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably comprises a composition. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably comprises a composite. In addition, the positive electrode active material refers to, for example, a particle collection of lithium cobalt nickel oxide.

[0053] In addition, when describing the characteristics of each particle of the positive electrode active material in the following embodiments, it is not necessary for all particles to have the characteristics. For example, as long as 50% or more, preferably 70% or more, and more preferably 90% or more of three or more positive electrode active material particles selected irregularly have the characteristics, it can be said that the positive electrode active material and the secondary battery containing the positive electrode active material have the effect of improving the characteristics.

[0054] Generally speaking, as the charging voltage of the secondary battery increases, the voltage of the positive electrode also increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at high voltage. The crystal structure of the positive electrode active material in the charged state is stable, so the reduction of the charge and discharge capacity due to repeated charge and discharge can be suppressed.

[0055] In addition, the short circuit of the secondary battery will not only cause defects in the charging and / or discharging operations of the secondary battery, but also cause heating and fire. In order to achieve a safe secondary battery, it is preferred to suppress the short-circuit current at a high charging voltage. The positive electrode active material of one embodiment of the present invention can also suppress the short-circuit current at a high charging voltage. Therefore, a secondary battery that simultaneously achieves high charge and discharge capacity and safety can be manufactured.

[0056] Note that unless otherwise specified, the state before deterioration of the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) contained in the secondary battery is described. Note that the following situation is not referred to as degradation: the case where the discharge capacity is reduced due to aging treatment and pre-burning treatment in the stage of manufacturing the secondary battery. For example, the following situation can be referred to as the state before deterioration: the case where the discharge capacity is 97% or more of the rated capacity of a lithium-ion secondary single cell and a lithium-ion secondary battery pack (hereinafter referred to as a lithium-ion secondary battery). In lithium-ion secondary batteries for portable devices, the rated capacity is based on JIS C 8711:2019. When using lithium-ion secondary batteries other than the above, it is not limited to the above-mentioned JIS specifications, but is based on various JIS, IEC standards, etc. for electric vehicle propulsion and industrial use.

[0057] In addition, in this specification, etc., the state before deterioration of the material contained in the secondary battery is sometimes referred to as an initial article or an initial state, and the state after deterioration (a state in which the discharge capacity is less than 97% of the rated capacity of the secondary battery) is sometimes referred to as an article in use or a state in use or a used article or a used state.

[0058] Note that in this specification, etc., the fire in the needle penetration test refers to a state in which an open flame is observed on the outside of the outer packaging. Alternatively, the fire refers to a state in which thermal runaway of the secondary battery occurs. For example, after the needle penetration test is completed, if thermal decomposition products of the positive electrode and / or the negative electrode are confirmed at a distance of more than 2 cm from the puncture part, this situation can be considered as a fire.

[0059] For example, when layered rock salt type LiMO2 is used as the positive electrode active material, the O / M (atomic ratio) is logically 2. On the other hand, when LiMO2 releases oxygen due to thermal runaway, the O / M (atomic ratio) decreases. Therefore, for example, when the O / M (atomic ratio) measured by EDX analysis at a place more than 2 cm away from the pierced part after the needle test is less than 1.3, it can also be said that thermal runaway, that is, fire, has occurred.

[0060] In addition, the thermal decomposition product of the positive electrode and / or the negative electrode includes, for example, aluminum oxide obtained by oxidizing aluminum of the positive electrode current collector and copper oxide obtained by oxidizing copper of the negative electrode current collector.

[0061] On the other hand, even if sparks and / or smoke are observed, the situation that the fire does not spread, that is, the situation that does not cause thermal runaway of the secondary battery as a whole, is not called a fire. For example, when the above-mentioned fire does not occur even when the secondary battery is subjected to a needle penetration test, the battery can be said to be a secondary battery that will not catch fire.

[0062] (Implementation Method 1) In this embodiment, refer to Figure 1A and Figure 1B A positive electrode active material 100 according to one embodiment of the present invention will be described.

[0063] Figure 1A and Figure 1B FIG. 1 is a cross-sectional view of a positive electrode active material 100 according to one embodiment of the present invention. Figure 1A As shown, the positive electrode active material 100 includes a surface portion 100a and an inner portion 100b. In the above figure, the boundary between the surface portion 100a and the inner portion 100b is indicated by a dotted line. Figure 1B The dot-dash line in the figure shows a part of the grain boundary 101. The (001) in the figure shows the (001) plane of lithium cobalt nickel oxide. 1-y Ni y O2 belongs to space group R-3m.

[0064] The positive electrode active material 100 preferably has high crystallinity. In addition, the positive electrode active material 100 is preferably a single particle (also referred to as a primary particle) rather than a secondary particle. In addition, the particle of the positive electrode active material 100 is more preferably a single crystal.

[0065] In this specification, the surface portion 100a of the positive electrode active material 100 refers to, for example, within 50nm from the surface to the inside, more preferably within 35nm from the surface to the inside, further preferably within 20nm from the surface to the inside, and most preferably within 10nm from the surface to the inside in a direction perpendicular or substantially perpendicular to the surface. Substantially perpendicular refers to more than 80° and less than 100°. In addition, the surface generated by cracks and fissures can also be referred to as a surface. The surface portion 100a is synonymous with the vicinity of the surface, the area near the surface, or the shell.

[0066] In addition, a region deeper than the surface layer portion 100a in the positive electrode active material is referred to as an inner portion 100b. The inner portion 100b is synonymous with an inner region or a core.

[0067] The surface of the positive electrode active material 100 refers to the surface of the composite oxide including the surface layer 100a and the inner part 100b. Therefore, the positive electrode active material 100 does not include: a material attached with a metal oxide such as aluminum oxide (Al2O3) that does not contain a lithium position that contributes to charging and discharging; carbonates, hydroxyl groups, etc. that are chemically adsorbed after the positive electrode active material is manufactured. In addition, the attached metal oxide refers to, for example, a metal oxide whose crystal structure is different from the crystal structure of the inner part 100b.

[0068] In addition, the electrolyte, organic solvent, binder, conductive material, or compounds derived from these materials that adhere to the positive electrode active material 100 are also not included.

[0069] In addition, the grain boundary 101 refers to, for example: a portion where the particles of the positive electrode active material 100 are bonded together; a portion where the crystal orientation changes inside the positive electrode active material 100, that is, a portion where the bright lines and dark lines in the STEM (Scanning Transmission Electron Microscope: Scanning Transmission Electron Microscope) image are repeatedly discontinuous, a portion containing multiple crystal defects, a portion with a disordered crystal structure, etc. In addition, a crystal defect refers to a defect that can be observed through a cross-sectional TEM image, a cross-sectional STEM image, etc., that is, a structure where atoms enter the lattice, a void, etc. The grain boundary 101 can be said to be a surface defect. In addition, the vicinity of the grain boundary 101 refers to the area within 10 nm from the grain boundary 101.

[0070] [Main Ingredients] In order to keep the charge neutral during the insertion and removal of lithium ions, the positive electrode active material of the lithium ion secondary battery needs to contain a transition metal that can be oxidized and reduced. The positive electrode active material 100 of one embodiment of the present invention preferably contains cobalt as the main component of the transition metal M that undergoes redox reaction. Note that in this specification, the main component of the transition metal M refers to the element with the highest atomic ratio in the transition metal M. Note that in the case of multiple transition metals M with the highest atomic ratio, the transition metal M can be said to be the main component. In addition, the positive electrode active material 100 preferably contains nickel in addition to cobalt. When nickel is included, the positive electrode active material can have high thermal stability at temperatures above room temperature, such as above 45°C, and more preferably above 65°C.

[0071] The positive electrode active material 100 of one embodiment of the present invention includes lithium, cobalt, nickel and oxygen. In addition, it is preferred to include an additive element. In addition, the positive electrode active material 100 preferably includes lithium nickel cobaltate (LiCo 1-y Ni y O2). Note that the positive electrode active material 100 of one embodiment of the present invention may have a crystal structure described below. Therefore, the composition of lithium cobalt nickel oxide is not strictly limited to Li: (Co + Ni): O = 1:1:2.

[0072] In addition, the ratio of nickel to the sum of cobalt and nickel is Ni / (Co+Ni), that is, LiCo 1-y Ni y The y in O2 is preferably greater than 0 and less than 0.5. In addition, it is more preferably greater than 0.1 and less than 0.3. Furthermore, it is further preferably greater than 0.025 and less than 0.215.

[0073] When Ni / (Co+Ni) is greater than 0.025 and less than 0.215, the + ) is not easy to generate CoO2(O1). Therefore, even if charging and discharging are repeated, it is not easy to cause the MO2 layer to shift, which can be considered to improve the stability of the crystal structure.

[0074] LiCo 1-y Ni y The case where y in O2 is 0.1 or more and 0.3 or less includes, for example, the case where Co:Ni=90:10 (atomic ratio), Co:Ni=80:20 (atomic ratio), or Co:Ni=70:30 (atomic ratio).

[0075] When the positive electrode active material 100 contains an additional element, as the additional element A, one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper, and gallium can be used.

[0076] When the added element A is too little, the positive electrode active material 100 cannot be chemically stabilized. However, when the added element A is too much, the charge-discharge capacity and the like may be negatively affected. Therefore, when the fluorine in the added element A that becomes an anion is denoted as F and other elements are typically denoted as A, the composition of the positive electrode active material 100 is expressed as LiCo 1-y- z Ni y A z O2F n In the case of , z+n is preferably greater than 0 and less than 0.1.

[0077] The additive element is preferably dissolved in the positive electrode active material 100. Therefore, when performing line analysis using STEM-EDX, for example, the depth at which the amount of the additive element detected increases is preferably deeper than the depth at which the amount of the transition metal M detected increases, i.e., on the inner side of the positive electrode active material 100.

[0078] In this specification, etc., the depth at which the detection amount of a certain element increases in the line analysis of STEM-EDX means the depth at which a single measurement value can be obtained continuously, and based on this measurement value, it can be judged that it is not noise from the perspective of intensity and spatial resolution.

[0079] The above-mentioned additional element further stabilizes the crystal structure of the positive electrode active material 100. Note that in this specification and the like, the additional element is synonymous with a mixture or a part of a raw material.

[0080] Note that magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper, or gallium does not necessarily need to be contained as an additive element.

[0081] 〔Crystal structure〕 Preferably, the positive electrode active material 100 of one embodiment of the present invention is in a discharged state, that is, in a Li x When x=1 in MO2, it has a layered rock salt type crystal structure belonging to the space group R-3m. The layered rock salt type composite oxide has a high discharge capacity and a two-dimensional diffusion path for lithium ions, which is suitable for the insertion / extraction reaction of lithium ions and is excellent as a positive electrode active material for secondary batteries. Therefore, the inner part 100b, which occupies most of the volume of the positive electrode active material 100, preferably has a layered rock salt type crystal structure.

[0082] On the other hand, the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has the following function: even if lithium is separated from the positive electrode active material 100 due to charging, the layered structure composed of the transition metal M and oxygen octahedrons in the interior 100b is strengthened to prevent the layered structure from collapsing. Alternatively, the surface portion 100a is preferably used as a barrier film of the positive electrode active material 100. Alternatively, the surface portion 100a of the outer peripheral portion of the positive electrode active material 100 preferably strengthens the positive electrode active material 100. Here, strengthening refers to the function of suppressing the detachment of oxygen and / or the deviation of the layered structure composed of the transition metal M and oxygen octahedrons, etc., of the surface portion 100a and the internal 100b of the positive electrode active material 100. And / in addition, strengthening refers to the function of suppressing the oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.

[0083] Therefore, the surface portion 100a preferably has a crystal structure different from that of the interior 100b. In addition, the composition and crystal structure of the surface portion 100a at room temperature (25°C) are preferably more stable than those of the interior 100b. For example, at least a portion of the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has the characteristics of both a layered rock salt type and a rock salt type crystal structure.

[0084] The surface part 100a is the area where lithium ions are first separated during charging, and is also an area where the lithium concentration is more likely to be lower than that of the inner part 100b. In addition, it can be said that part of the bonds among the atoms on the surface of the particles of the positive electrode active material 100 contained in the surface part 100a are cut. Therefore, the surface part 100a can be said to be an area that is prone to become unstable and where crystal structure degradation is likely to begin. For example, it is believed that: in the surface part 100a, when the crystal structure of the layered structure composed of the octahedron of the transition metal M and oxygen deviates, its influence extends to the inner part 100b and the crystal structure of the layered structure also deviates in the inner part 100b, resulting in degradation of the overall crystal structure of the positive electrode active material 100. On the other hand, as long as the surface part 100a can be made sufficiently stable, even in the case of Li x When x in MO2 is small, the layered structure composed of transition metal M and oxygen octahedrons in the inner 100b can be prevented from collapsing. In addition, the deviation of the layer composed of transition metal M and oxygen octahedrons in the inner 100b can be suppressed. x The case where x in MO2 is small refers to the case where x is 0.24 or less, for example.

[0085] 〔Distribution of added elements〕 In order to make the surface part 100a have a chemically stable composition and crystal structure, the surface part 100a preferably contains an added element, and more preferably contains a plurality of added elements. In addition, the average value of the detected amount of one or more selected from the added elements of the surface part 100a is preferably higher than that of the internal 100b. In addition, one or more selected from the added elements contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, it is more preferred that the distribution of the added elements in the positive electrode active material 100 is different. For example, it is more preferred that the depth of the detected amount peak in the surface part from the surface or the reference point of the EDX line analysis described later is different according to the added element. Here, the detected amount peak refers to the maximum value of the detected amount of the surface part 100a or 50nm below the surface. The detected amount refers to the calculation in the EDX line analysis, for example.

[0086] Preferably, the surface portion 100a and the inner portion 100b contain the same main component (here, cobalt), and the surface portion 100a and the inner portion 100b are connected to each other. By adopting the above structure, since the surface portion 100a protects the inner portion 100b, the excellent effect of internal short circuit is exerted when the above structure is used in a secondary battery. For example, in the case where a nail or the like pierces the secondary battery from the outside, since the surface portion 100a is included, it can be said that the positive electrode active material has a structure that does not catch fire or is difficult to catch fire.

[0087] For example, when the average of the detection value of one of the added elements such as fluorine in the surface portion 100a is higher than the average in the inner portion 100b, the excessive reaction of the positive electrode active material 100 and the electrolyte can be suppressed. Thus, when the secondary battery is used, it can be expected that the safety of the internal short circuit of the secondary battery can be improved. In addition, the corrosion resistance to hydrofluoric acid can be effectively improved.

[0088] In addition, it is more preferable that when the average of the detected amounts of one or more selected from the added elements in the surface portion 100a is higher than the average in the inner portion 100b, the conductivity of the surface of the positive electrode active material 100 changes. For example, it is preferable that the powder resistance of the positive electrode active material 100 is improved. By using a positive electrode active material 100 with a high powder resistance, it can be expected that the safety of the secondary battery against internal short circuits, etc., can be improved when used in a secondary battery.

[0089] [Differences in the distribution of added elements on each crystal plane] Note that the added element does not need to have the same concentration gradient or distribution throughout the surface layer 100a of the positive electrode active material 100. As an example of the depth direction of the crystal plane other than the (001) plane of lithium cobalt nickel oxide of one embodiment of the present invention, Figure 1A Arrows X1-X2 are shown in FIG. 1 and arrows Y1-Y2 are shown as examples of the depth direction of the (001) plane.

[0090] The distribution of the added elements of the surface parallel to (001) of the positive electrode active material 100 may also be different from other surfaces. For example, compared with the surface other than the (001) orientation shown by the arrows X1-X2, the average of the detected amount of one or more of the added elements selected from the surface parallel to the (001) shown by the arrows Y1-Y2 and its surface portion 100a may also be low. In addition, the concentration of one or more of the added elements selected from the surface parallel to (001) and its surface portion 100a may also be lower than 1 atomic%. In addition, the detected amount peak of one or more of the added elements selected from the surface parallel to (001) and its surface portion 100a may also be located at a shallow position from the surface compared with the surface other than the (001) orientation.

[0091] In the layered rock salt type crystal structure belonging to R-3m, cations are arranged parallel to the (001) plane. It can be said that this is a structure in which MO2 layers and lithium layers are stacked alternately parallel to the (001) plane. Therefore, the diffusion path of lithium ions is also parallel to the (001) plane.

[0092] The MO2 layer is relatively stable, and therefore relatively stable when the surface of the positive electrode active material 100 is oriented in the (001) direction. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) surface.

[0093] On the other hand, on the surface other than the (001) orientation, the diffusion path of lithium ions is exposed. Therefore, the surface other than the (001) orientation and its surface portion 100a are important areas for maintaining the diffusion path of lithium ions, and are the areas where lithium ions first leave, so they tend to be unstable. Therefore, in order to maintain the overall crystal structure of the positive electrode active material 100, it is very important to strengthen the surface other than the (001) orientation and its surface portion 100a.

[0094] In the following embodiment, when producing high-purity LiCo 1-y Ni y In the manufacturing method of mixing the additive element with O2 and then heating, the additive element diffuses mainly through the diffusion path of lithium ions. Therefore, it is easy to set the distribution of the additive element in the surface other than the (001) orientation and the surface layer 100a to a preferred range.

[0095] In addition, as an example of the depth direction of the (001) plane generated by sliding the positive electrode active material 100 in parallel with the (001) plane, Figure 1BArrows Z1-Z2 are shown in FIG. Arrows Z1-Z2 are also the same as the plane parallel to (001) shown by arrows Y1-Y2. That is, the average of the detected amounts of one or more selected from the added elements can also be lower than the surface oriented other than (001). In addition, the concentration of one or more selected from the added elements can also be lower than 1 atomic %.

[0096] When a plurality of additive elements are contained as described above, each additive element synergistically contributes to further stabilization of the surface layer portion 100 a .

[0097] Note that it is not preferred that the surface layer 100a only contains a compound of the added element and oxygen because lithium is not easily inserted and removed. Therefore, the surface layer 100a needs to contain at least cobalt or nickel, contain lithium in the discharge state, and have a path for lithium insertion and removal.

[0098] In order to sufficiently ensure a path for insertion and extraction of lithium, it is preferable that the total amount of cobalt and nickel detected in the surface layer portion 100 a is higher than that of the added element.

[0099] 〔Generally consistent〕 In addition, it is preferable that the crystal structure changes continuously from the inner portion 100b to the surface due to the concentration gradient of the added element. Alternatively, it is preferable that the crystal orientations of the surface portion 100a and the inner portion 100b are substantially the same.

[0100] For example, it is preferred that the crystal structure changes continuously from the inner part 100b of the layered rock salt type to the surface and the surface layer 100a of the rock salt type or having both characteristics of the rock salt type and the layered rock salt type. Alternatively, it is preferred that the surface layer 100a of the rock salt type or having both characteristics of the rock salt type and the layered rock salt type and the inner part 100b of the layered rock salt type have substantially the same orientation.

[0101] In addition, in this specification, etc., the layered rock salt type crystal structure belonging to the space group R-3m possessed by the composite oxide containing lithium and transition metal M refers to the following crystal structure: having a rock salt type ion arrangement in which cations and anions are alternately arranged, and the transition metal M and lithium are regularly arranged to form a two-dimensional plane, so that lithium can diffuse in two dimensions. In addition, defects such as vacancies of cations or anions may also be included. Strictly speaking, the layered rock salt type crystal structure is sometimes a structure formed by deformation of the lattice of the rock salt type crystal.

[0102] In addition, the rock salt type crystal structure has a cubic crystal structure such as space group Fm-3m, in which cations and anions are arranged alternately. In addition, vacancies of cations or anions may also be included.

[0103] In addition, whether or not the crystal has the characteristics of both the layered rock salt type crystal structure and the rock salt type crystal structure can be determined by electron diffraction, TEM images, cross-sectional STEM images, and the like.

[0104] There is no difference in the position of cations in the rock salt type crystal structure, but there are two types of cation positions in the layered rock salt type crystal structure, one is the position where lithium occupies most of the position and the other is the position where the transition metal M occupies. Both the rock salt type and the layered rock salt type have a stacked structure in which the two-dimensional planes of cations and the two-dimensional planes of anions are arranged alternately. In the bright spots of the electron diffraction pattern of the crystal plane forming the above-mentioned two-dimensional plane, when the central spot (transmitted spot) is taken as the origin 000, the bright spot closest to the central spot is, for example, located on the (111) plane of the rock salt type crystal structure or the (003) plane of the layered rock salt type crystal structure in an ideal state. For example, when comparing the electron diffraction patterns of rock salt type MgO and layered rock salt type LiCoO2, the distance between the bright spots on the (003) plane of LiCoO2 is observed to be about half the distance between the bright spots on the (111) plane of MgO. Therefore, for example, when the analysis area includes two phases of rock salt type MgO and layered rock salt type LiCoO2, there are plane orientations in which bright spots of stronger brightness and bright spots of weaker brightness are arranged alternately in the electron diffraction pattern. Bright spots common to the rock salt type and the layered rock salt type have high brightness, while bright spots only emitted in the layered rock salt type have low brightness.

[0105] In addition, in cross-sectional STEM images, when observing the layered rock salt type crystal structure from a direction perpendicular to the c-axis, layers with higher brightness and layers with lower brightness are observed alternately. The positions of the cations of the rock salt type are the same, so the above characteristics cannot be observed. When a crystal structure having characteristics of both the rock salt type and the layered rock salt type is used, when observing from a specific crystal orientation, layers with higher brightness and layers with lower brightness are observed alternately in cross-sectional STEM images, and a metal with an atomic number greater than lithium exists in a part of the lower brightness layer, that is, the lithium layer.

[0106] The anions of the layered rock salt type crystal and the rock salt type crystal form a cubic closest packing structure (face-centered cubic lattice structure) respectively. Therefore, when the layered rock salt type crystal and the rock salt type crystal come into contact, there are crystal planes with the same orientation of the cubic closest packing structure formed by the anions.

[0107] In addition, it can be explained as follows. The anions on the (111) plane of the cubic crystal structure have a triangular lattice. The layered rock salt type has a rhombus structure belonging to the space group R-3m, but in order to facilitate the understanding of the structure, it is usually shown as a composite hexagonal lattice, and the (0001) plane of the layered rock salt type has a hexagonal lattice. The triangular lattice of the (111) plane of the cubic crystal has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock salt type. The state in which the lattices of the two are integrated can be said to be a state in which the orientation of the cubic closest packing structure is consistent.

[0108] Note that the space group of the layered rock salt type crystal is R-3m, which is different from the space group Fm-3m (the space group of the general rock salt type crystal) of the rock salt type crystal, so the Miller index of the crystal face that satisfies the above conditions is different between the layered rock salt type crystal and the rock salt type crystal. In this specification, sometimes the state of the orientation of the cubic closest packing structure composed of anions in the layered rock salt type crystal and the rock salt type crystal is consistent with each other refers to the state of roughly consistent crystal orientation. In addition, the state of having similarities in three-dimensional structures such as roughly consistent crystal orientation or having the same orientation in crystallography is called topological derivative (topotaxy).

[0109] When judging whether the crystal orientations of two regions are roughly consistent, TEM (Transmission Electron Microscope: Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope: Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM: High-angle annular dark field) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope: Annular Bright Field Scanning Transmission Electron Microscope) images, electron diffraction patterns, etc. can be used. In addition, the FFT pattern of the TEM image and the FFT pattern of the STEM image can also be used for judgment. In addition, XRD (X-ray Diffraction: X-ray diffraction), neutron diffraction, etc. can be used as a basis for judgment.

[0110] Figure 2 An example of a TEM image showing that the orientations of the layered rock salt type crystals LRS and the rock salt type crystals RS are substantially consistent is shown. TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc. can be used to obtain images reflecting the crystal structure.

[0111] For example, the contrast derived from the crystal plane can be obtained from a high-resolution TEM image. Due to the diffraction and interference of the electron beam, for example, when the electron beam is incident perpendicularly to the c-axis of the layered rock salt type composite hexagonal lattice, a repetition of high contrast bands (bright band lines) and dark bands (dark band lines) derived from the (0003) plane can be obtained. Therefore, the repetition of bright and dark lines is observed in the TEM image, and between the bright lines (for example, Figure 2 L RS and L LRS ) is less than 5 degrees or less than 2.5 degrees, it can be judged that the crystal planes are roughly consistent, that is, the crystal orientations are roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the crystal orientations are roughly consistent.

[0112] In addition, in the HAADF-STEM image, a contrast ratio proportional to the atomic number is obtained, and the larger the atomic number of the element, the brighter it is observed. For example, when using a layered rock salt type lithium cobalt nickel oxide belonging to the space group R-3m, the atomic numbers of cobalt (atomic number 27) and nickel (atomic number 28) are large, so the electron beam is more strongly scattered at the positions of cobalt atoms and nickel atoms, so that the arrangement of cobalt atoms and nickel atoms is observed as an arrangement of bright lines or high-brightness points. Therefore, when observing lithium cobalt nickel oxide with a layered rock salt type crystal structure from a direction perpendicular to the c-axis, the arrangement of cobalt atoms and nickel atoms in the direction perpendicular to the c-axis is observed as an arrangement of bright lines or points with higher brightness, and the arrangement of lithium atoms and oxygen atoms is observed as dark lines or areas with lower brightness. The same is true when fluorine (atomic number 9) and magnesium (atomic number 12) are included as additive elements of lithium cobalt nickel oxide.

[0113] Therefore, in the HAADF-STEM image, when the repetition of bright and dark lines is observed in two regions with different crystal structures, when the angle between the bright lines is less than 5 degrees or less than 2.5 degrees, it can be judged that the atomic arrangement is roughly consistent, that is, the crystal orientation is roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the crystal orientation is roughly consistent.

[0114] In addition, in ABF-STEM, elements with smaller atomic numbers appear brighter, but a contrast corresponding to the atomic number can be obtained similarly to HAADF-STEM, so the orientation of the crystal can be determined similarly to the HAADF-STEM image.

[0115] Figure 3A An example of a STEM image showing that the orientations of the layered rock salt type crystals LRS and the rock salt type crystals RS are substantially consistent with each other. Figure 3B The FFT pattern of the region showing the rock salt type crystal RS, Figure 3C FFT pattern of a region showing layered rock-salt type crystals LRS. Figure 3B and Figure 3C The composition, JCPDS card number, and d value and angle to be calculated are shown on the left. The measured value is shown on the right. The spot with O indicates the zero-order diffraction.

[0116] exist Figure 3B The spots marked with A in the figure come from the 11-1 reflection of the cubic crystal. Figure 3C The spots marked with A in the figure are from the 0003 reflection of the layered rock salt type. Figure 3B and Figure 3C It can be seen that the orientation of the 11-1 reflection of the cubic crystal is roughly consistent with the orientation of the 0003 reflection of the layered rock salt type. Figure 3B The straight line of AO and the Figure 3C The straight lines of AO are roughly parallel. The roughly consistent and roughly parallel described here refer to the case where the angle is less than 5 degrees or less than 2.5 degrees.

[0117] As described above, in the FFT pattern and the electron diffraction pattern, when the orientations of the layered rock salt type crystals and the rock salt type crystals are approximately the same, the layered rock salt type <0003> The orientation is roughly consistent with the <11-1> orientation of the rock salt type. At this time, their reciprocal points are preferably spot-shaped, that is, not continuous with other reciprocal points. The reciprocal points are spot-shaped and not continuous with other reciprocal points, which means that the crystallinity is high.

[0118] In addition, as described above, when the orientation of the 11-1 reflection of the cubic crystal is roughly the same as the orientation of the 0003 reflection of the layered rock salt type, a spot that does not originate from the 0003 reflection of the layered rock salt type is sometimes observed in a reciprocal space different from the orientation of the 0003 reflection of the layered rock salt type, depending on the incident orientation of the electron beam. Figure 3C The spot with B in the figure is from the 10-14 reflection of the layered rock salt type. This spot is sometimes located at the reciprocal point ( Figure 3C When viewed from the direction of A), the angle is greater than 52° and less than 56° (i.e., ∠AOB is greater than 52° and less than 56°) and d is greater than 0.19nm and less than 0.21nm. Note that the above index is only an example and does not need to be consistent with the index. For example, reciprocal grid points equivalent to 0003 and 1014 can also be used.

[0119] Similarly, a spot not derived from the 11-1 reflection of a cubic crystal is sometimes observed in a reciprocal space different from the orientation at which the 11-1 reflection of a cubic crystal is observed. Figure 3B The spots in the figure are from the 200 reflection of the cubic crystal. Sometimes, in the reflection from the 11-1 ( Figure 3BThe diffraction spots are observed at locations where the angle is greater than 54° and less than 56° (i.e., ∠AOB is greater than 54° and less than 56°) when viewed from the azimuth of A). Note that the above index is only an example and does not need to be consistent with the index. For example, reciprocal grid points equivalent to 11-1 and 200 may also be used.

[0120] Note that it is known that in layered rock salt-type positive electrode active materials such as lithium cobalt nickel oxide, the (0003) plane and its equivalent plane and the (10-14) plane and its equivalent plane are easy to present as crystal planes. Therefore, when carefully observing the shape of the positive electrode active material using SEM, for example, in TEM, etc., the observation sample is thinned using FIB (Focused Ion Beam) in a manner such that the electron beam is incident (incidence) at [1-210) so that the (0003) plane is easy to observe. When it is necessary to determine the consistency of the crystal orientation, it is preferred to thin the sample so that the (0003) plane of the layered rock salt type is easy to observe.

[0121] 〔Grain boundary〕 When the positive electrode active material 100 according to one embodiment of the present invention contains an additional element, it is preferred that at least a part of the additional element is distributed unevenly at the grain boundary 101 and its vicinity in addition to the distribution described above.

[0122] In this specification, etc., "non-uniformly distributed" means that the concentration of an element in an arbitrary region is different from that in other regions. "Non-uniformly distributed" is synonymous with "segregation", "precipitation", "non-uniform", "deviation", and "mixture of high-concentration regions and low-concentration regions".

[0123] For example, it is preferable that the average of the detected amount of the added element in the grain boundary 101 and the vicinity thereof in the positive electrode active material 100 is higher than the average of the amount other than the vicinity thereof in the grain boundary 101 of the inner portion 100 b .

[0124] The grain boundary 101 is a surface defect. Therefore, it tends to be unstable and easily starts to change the crystal structure like the particle surface. Therefore, the higher the concentration of the added element in the grain boundary 101 and its vicinity, the more effectively the change of the crystal structure can be suppressed.

[0125] 〔Li x Crystal structure when x in MO2 is small] The positive electrode active material 100 of one embodiment of the present invention is in a charged state, that is, in a Li x When x in MO2 is small, it preferably has the following crystal structure.

[0126] Ni / (Co+Ni) is greater than 0.175 and less than 0.215, typically 0.2. When the positive electrode active material 100 is charged to 4.5V (vs. Li / Li +) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it is preferred that at least two of 2θ=18.526±0.1°, 2θ=37.391±0.1°, 2θ=37.628±0.1°, 2θ=39.015±0.1°, 2θ=44.947±0.1°, 2θ=49.029±0.1° and 2θ=58.857±0.1° have diffraction peaks. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is In addition, the crystal grain size is preferably 100 nm or more, and more preferably 150 nm or more. Note that in this specification, etc., A±B means (AB) or more and (A+B) or less.

[0127] In addition, when the positive electrode active material 100 has a Ni / (Co+Ni) ratio greater than 0.175 and less than 0.215, typically 0.2, it is charged to 4.6 V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at least two of 2θ=18.351±0.1°, 2θ=37.412±0.1°, 2θ=38.974±0.1°, 2θ=44.865±0.1°, 2θ=48.864±0.1° and 2θ=58.621±0.1° have diffraction peaks. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 70 nm or more, and more preferably 90 nm or more.

[0128] In addition, when the positive electrode active material 100 has a Ni / (Co+Ni) ratio greater than 0.175 and less than 0.215, typically 0.2, it is charged to 4.7 V (vs. Li / Li +) is analyzed by X-ray powder diffraction using CuKα1 line, preferably, it has diffraction peaks at at least two of 2θ=18.382±0.1°, 2θ=37.391±0.1° and 2θ=44.886±0.1°. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is In addition, the crystal grain size is preferably 80 nm or more, and more preferably 100 nm or more.

[0129] In addition, the positive electrode active material 100 wherein Ni / (Co+Ni) is greater than 0.175 and less than 0.215, typically 0.2, and contains 0.5 atomic % of magnesium as a transition metal M and 1.5 atomic % of fluorine as a transition metal M as an additive element, when charged to 4.5 V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at 2θ=18.516±0.1°, 2θ=37.391±0.1°, 2θ=37.586±0.1°, 2θ=38.995±0.1°, 2θ=44.947±0.1°, 2θ=49.039±0.1° and 2θ=58.898±0.1°. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 100 nm or more, and more preferably 150 nm or more.

[0130] In addition, the positive electrode active material 100 containing 0.5 atomic % of magnesium as transition metal M and 1.5 atomic % of fluorine as transition metal M as an additive element is charged to 4.6 V (vs. Li / Li +) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at 2θ=18.608±0.1°, 2θ=37.381±0.1°, 2θ=37.792±0.1°, 2θ=39.015±0.1°, 2θ=44.999±0.1°, 2θ=49.101±0.1° and 2θ=58.991±0.1°. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 50 nm or more, and more preferably 70 nm or more.

[0131] Ni / (Co+Ni) is greater than 0.175 and less than 0.215, typically 0.2, and the positive electrode active material 100 manufactured by annealing after synthesizing lithium cobalt nickel oxide is charged to 4.5V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at least two of 2θ=18.403±0.1°, 2θ=37.412±0.1°, 2θ=38.985±0.1°, 2θ=44.875±0.1°, 2θ=48.916±0.1° and 2θ=58.662±0.1° have diffraction peaks. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 100 nm or more, and more preferably 130 nm or more.

[0132] In addition, the positive electrode active material 100 in which Ni / (Co+Ni) is greater than 0.175 and less than 0.215, typically 0.2, and the positive electrode active material 100 manufactured by annealing after synthesizing lithium cobalt nickel oxide is charged to 4.6 V (vs. Li / Li +) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at least two of 2θ=18.608±0.1°, 2θ=37.381±0.1°, 2θ=37.854±0.1°, 2θ=38.995±0.1°, 2θ=45.009±0.1° and 2θ=59.073±0.1° have diffraction peaks. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 50 nm or more, and more preferably 75 nm or more.

[0133] In addition, the positive electrode active material 100 in which Ni / (Co+Ni) is greater than 0.175 and less than 0.215, typically 0.2, and the positive electrode active material 100 manufactured by annealing after synthesizing lithium cobalt nickel oxide is charged to 4.7 V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably, it has diffraction peaks at at least two of 2θ=18.413±0.1°, 2θ=36.774±0.1°, 2θ=37.412±0.1° and 2θ=44.958±0.1°. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 50 nm or more, and more preferably 75 nm or more.

[0134] Ni / (Co+Ni) is greater than 0.075 and less than 0.125, typically 0.1. When the positive electrode active material 100 is charged to 4.5V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at 2θ=18.434±0.1°, 2θ=37.401±0.1°, 2θ=39.005±0.1°, 2θ=44.896±0.1°, 2θ=48.957±0.1° and 2θ=58.744±0.1°. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 100 nm or more, and more preferably 130 nm or more.

[0135] In addition, when the positive electrode active material 100 has a Ni / (Co+Ni) ratio of greater than 0.075 and less than 0.125, typically 0.1, it is charged to 4.6 V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably, it has diffraction peaks at at least two of 2θ=18.567±0.1°, 2θ=37.381±0.1°, 2θ=39.005±0.1° and 2θ=44.978±0.1°. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 30 nm or more, and more preferably 45 nm or more.

[0136] In addition, the positive electrode active material 100 wherein Ni / (Co+Ni) is greater than 0.075 and less than 0.125, typically 0.1, and contains 0.5 atomic % of magnesium as a transition metal M and 1.5 atomic % of fluorine as a transition metal M as an additive element, when charged to 4.5 V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at 2θ=18.537±0.1°, 2θ=37.391±0.1°, 2θ=37.658±0.1°, 2θ=39.005±0.1°, 2θ=44.958±0.1°, 2θ=49.039±0.1° and 2θ=58.898±0.1°. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 100 nm or more, and more preferably 150 nm or more.

[0137] In addition, the positive electrode active material 100 containing 0.5 atomic % of magnesium as transition metal M and 1.5 atomic % of fluorine as transition metal M as an additive element is charged to 4.6 V (vs. Li / Li + ) is analyzed by X-ray powder diffraction using CuKα1 line, preferably at least two of 2θ=18.547±0.1°, 2θ=37.381±0.1°, 2θ=38.985±0.1°, 2θ=44.978±0.1°, 2θ=49.101±0.1° and 2θ=59.073±0.1° have diffraction peaks. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 50 nm or more, and more preferably 75 nm or more.

[0138] Ni / (Co+Ni) is greater than 0.025 and less than 0.075, typically 0.05. When the positive electrode active material 100 is charged to 4.5V (vs. Li / Li + ) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it is preferred that at least two of 2θ=18.567±0.1°, 2θ=37.381±0.1°, 2θ=37.710±0.1°, 2θ=38.985±0.1°, 2θ=44.968±0.1°, 2θ=49.070±0.1° and 2θ=58.980±0.1° have diffraction peaks. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 100 nm or more, and more preferably 150 nm or more.

[0139] In addition, when the positive electrode active material 100 has a Ni / (Co+Ni) ratio greater than 0.025 and less than 0.075, typically 0.05, it is charged to 4.6 V (vs. Li / Li +) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it is preferred that at least two of 2θ=18.866±0.1°, 2θ=37.319±0.1°, 2θ=38.337±0.1°, 2θ=38.985±0.1°, 2θ=45.143±0.1°, 2θ=49.368±0.1° and 2θ=59.515±0.1° have diffraction peaks. In addition, it is preferred that the positive electrode active material 100 has a crystal structure belonging to the space group R-3m, and the lattice constant of the crystal structure is And the unit cell volume is Furthermore, it is more preferred that the lattice constant is And the unit cell volume is Furthermore, the crystal grain size is preferably 150 nm or more, and more preferably 200 nm or more.

[0140] <Analysis Method> In order to determine whether a certain positive electrode active material is a positive electrode active material 100 of one embodiment of the present invention having the above-mentioned crystal structure in a charged state, the positive electrode containing the positive electrode active material in a charged state can be judged by analyzing using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc.

[0141] In particular, XRD is preferred because of the following advantages: the symmetry of transition metals such as cobalt in the positive electrode active material can be analyzed with high resolution; the height of crystallinity and the orientation of the crystal can be compared; the periodic distortion of the lattice and the grain size can be analyzed; sufficient accuracy can be obtained when directly measuring the positive electrode obtained by disassembling a secondary battery, etc. Through XRD, especially powder XRD, a diffraction peak reflecting the crystal structure of the interior 100b of the positive electrode active material 100 that occupies most of the volume of the positive electrode active material 100 can be obtained.

[0142] When analyzing the crystal size by powder XRD, it is preferable to perform the measurement excluding the influence of orientation due to pressure, etc. For example, it is preferable to take out the positive electrode active material from the positive electrode obtained by disassembling the secondary battery as a powder sample for measurement.

[0143] However, the positive electrode active material in a charged state may change its crystal structure when exposed to the atmosphere. Therefore, all samples used in analyzing the crystal structure are preferably treated in an inert atmosphere such as an argon atmosphere.

[0144] In addition, by analyzing by XPS, Energy Dispersive X-ray Spectroscopy (EDX), EPMA (Electron Probe Microanalysis), or the like, it can be determined whether the distribution of the additional elements contained in a positive electrode active material is in the above-mentioned state.

[0145] The crystal structure of the surface layer portion 100 a , the grain boundary 101 , and the like can be analyzed by performing electron diffraction or the like on a cross section of the positive electrode active material 100 .

[0146] <<Charging Method>> In order to determine whether a certain positive electrode active material or a certain composite oxide is the positive electrode active material 100 of one embodiment of the present invention, it is necessary to charge the positive electrode active material to a predetermined potential (vs. Li / Li + For this purpose, for example, a reference battery using a lithium counter electrode, a coin battery (CR2032 type, 20 mm in diameter, 3.2 mm in height), or the like is manufactured and charged.

[0147] More specifically, as the positive electrode, a positive electrode obtained by applying a slurry obtained by mixing a positive electrode active material, a conductive material, and a binder to a positive electrode current collector of an aluminum foil can be used.

[0148] As the electrolyte contained in the electrolytic solution, 1 mol / L lithium hexafluorophosphate (LiPF6) is used. As the electrolytic solution, a solution of ethylene carbonate (EC): diethyl carbonate (DEC) = 3:7 (volume ratio) and a mixture of EC and DEC and 2 wt% of vinylene carbonate (VC) can be used.

[0149] The coin cell manufactured under the above conditions is charged at any voltage (for example, 4.5V, 4.6V or 4.7V). As long as charging can be performed at any voltage and for a sufficient time, there is no limitation on the charging method. For example, when charging with CCCV, the current in CC charging can be set to be greater than 20mA / g and less than 100mA / g. CV charging can be performed until it is greater than 2mA / g and less than 10mA / g. In order to observe the phase change of the positive electrode active material, it is preferred to charge at the above-mentioned smaller current value. On the other hand, when the current does not become greater than 2mA / g and less than 10mA / g even if CV charging is performed for a long time, it can be considered that the current consumption is in the decomposition of the electrolyte rather than in the charging of the positive electrode active material, so the CV charging can also be ended at a point in time after a sufficient time has passed since the start of CV charging. At this time, the sufficient time can be, for example, greater than 1.5 hours and less than 3 hours. The temperature is set to 25°C or 45°C. After charging in this way, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode active material of any charge capacity. When various analyses are performed later, in order to prevent reaction with external components, it is preferably sealed under an argon atmosphere. For example, XRD can be performed under the condition of a sealed container sealed in an argon atmosphere. In addition, it is preferred to take out the positive electrode immediately after charging for analysis. Specifically, it is preferably performed within 1 hour after charging, and more preferably within 30 minutes after charging.

[0150] < <xrd>> There is no limitation on the apparatus and conditions for XRD measurement as long as there is appropriate adjustment and calibration. For example, the measurement can be performed with the following apparatus and conditions. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: Cu Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 90° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm As a standard sample for adjustment and calibration, for example, a standard sintered alumina plate SRM 1976 of NIST (National Institute of Standards and Technology) or the like can be used.

[0151] When the sample to be measured is a powder, the sample can be mounted by placing the sample on a glass sample holder; or sprinkling the sample on a silicon non-reflective plate coated with grease; etc. When the sample to be measured is a positive electrode, the positive electrode active material layer can be mounted according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.

[0152] As a monochromatic method for characteristic X-rays, a thin film or the like may be used, or XRD data analysis software may be used after obtaining the XRD pattern. For example, DEFFRAC.EVA (XRD data analysis software manufactured by Bruker) may be used to remove the peak of the CuKα2 line and extract only the peak of the CuKα1 line. In addition, by using this software, the background or the like may also be removed.

[0153] In this specification, when describing the value of 2θ of a certain diffraction peak, the value refers to the value of 2θ when the peak top of the diffraction peak appears in the XRD pattern after fitting the calculation model. There is no particular limitation on the crystal structure analysis software used for fitting, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker) can be used.

[0154] < <edx>> One or two of the selected added elements contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, the positive electrode active material 100 preferably has a different depth from the surface of the peak of the detected amount according to the added element. The concentration gradient of the added element can be evaluated by, for example, exposing the cross section of the positive electrode active material 100 by FIB (Focused Ion Beam) or the like and analyzing the cross section using energy dispersive X-ray spectrometry (EDX), EPMA (electron probe microanalysis), etc.

[0155] In EDX measurement, the method of measuring while scanning in a region to evaluate in two dimensions is called EDX surface analysis. In addition, the method of evaluating the atomic concentration distribution in the positive electrode active material by linear scanning and measuring is called line analysis. Sometimes the method of extracting the data of the linear region from the surface analysis of EDX is called line analysis. In addition, the method of measuring without scanning in a certain region is called point analysis.

[0156] By EDX surface analysis (e.g., element mapping), the concentration and detection amount of the added elements in the surface portion 100a, the interior 100b, and the vicinity of the grain boundary 101 of the positive electrode active material 100 can be quantitatively analyzed. In addition, by EDX line analysis, the concentration distribution and maximum value of the added elements can be analyzed. In addition, in the analysis of thinning the sample as in STEM-EDX, the concentration distribution in the depth direction from the surface of the positive electrode active material in a specific area to the center can be analyzed without being affected by the distribution in the depth direction, so it is preferred.

[0157] The positive electrode active material 100 is a compound containing transition metal and oxygen in which lithium can be inserted and removed, so the interface between the region where there is a transition metal M (e.g., Co, Ni, Mn, Fe, etc.) and oxygen that are oxidized and reduced with the insertion and removal of lithium and the region where there is no transition metal M and oxygen is called the surface of the positive electrode active material. When analyzing the positive electrode active material, the surface is sometimes covered with a protective film, but the protective film is not included in the positive electrode active material. As a protective film, a single layer or multilayer film of carbon, metal, oxide, resin, etc. is sometimes used.

[0158] In STEM-EDX line analysis, the element distribution does not change dramatically in principle or due to measurement errors, and it is sometimes difficult to strictly determine the surface. Therefore, when the depth direction is involved in STEM-EDX line analysis, the value of the detected amount of the transition metal M is equal to the average value M of the detected amount inside. AVE and the background average M BG The point where the total of 50% of the oxygen detected is equal to the average value of the internal detection amount O AVE and the background average O BG The point where the total of the transition metal M and oxygen is 50% of the total of the background is taken as the reference point. In addition, it is considered that the fact that the points where the total of the transition metal M and oxygen are different from each other is due to the influence of metal oxides and carbonates containing oxygen attached to the surface, so the average value M of the detected amount inside the transition metal M can be used. AVE and the background average M BG When a positive electrode active material including a plurality of transition metals M is used, the M of the element with the largest count in the inner 100b can be used. AVE and M BG Determine the above reference point.

[0159] The average value M of the background of the above transition metal M BG For example, it can be obtained by averaging the range of 2 nm or more, preferably 3 nm or more, outside the positive electrode active material near the portion where the detected amount of transition metal M starts to increase. AVE The average value of the background value of oxygen can be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, in a region where the counts of transition metal M and oxygen are saturated and stabilized, such as a region where the detection amount of transition metal M begins to increase to a depth of 30 nm or more, preferably to a depth of more than 50 nm. BG and the average value of the amount of oxygen detected inside AVE It can also be found in the same way.

[0160] In addition, the surface of the positive electrode active material 100 in the cross-sectional STEM (scanning transmission electron microscope) image, etc. refers to: the boundary between the region where the image of the crystal structure derived from the positive electrode active material is observed and the region where the image is not observed, and refers to the outermost side of the region where the atomic column of the nucleus of the metal element having an atomic number greater than lithium in the metal element constituting the positive electrode active material is confirmed. Alternatively, the surface of the positive electrode active material 100 refers to: the intersection of the tangent line drawn from the surface to the bulk in the STEM image and the axis in the depth direction. The surface in the STEM image, etc. can also be judged by referring to an analysis with a higher spatial resolution.

[0161] In addition, the spatial resolution of STEM-EDX is about 1 nm. Therefore, it is possible that the maximum value of the additive element distribution also deviates by about 1 nm. For example, when the maximum value of the additive element distribution such as magnesium is located outside the surface calculated above, as long as the difference between the maximum value and the surface is less than 1 nm, it can be regarded as an error.

[0162] In addition, the peak in STEM-EDX line analysis refers to the maximum value of the detection intensity in each element distribution or the characteristic X-ray of each element. As noise in STEM-EDX line analysis, it can be considered to be the measured value of the half width below the spatial resolution (R), for example, below R / 2.

[0163] By scanning the same part multiple times under the same conditions, the influence of noise can be reduced. For example, the cumulative value of six scans can be used as the distribution of each element. The number of scans is not limited to six, and more than six scans can be performed and the average is used as the distribution of each element.

[0164] STEM-EDX line analysis can be performed, for example, by the following steps: First, a protective film is deposited on the surface of the positive electrode active material by evaporation, for example, carbon can be deposited by an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies Corporation).

[0165] Next, the positive electrode active material is thinned to produce a STEM cross-sectional sample. For example, thinning can be performed by a FIB-SEM device (XVision200TBS manufactured by Hitachi High-Technologies Corporation). At this time, MPS (microprobe system) can be used for picking up, and as the final processing, for example, an accelerating voltage of 10 kV can be used.

[0166] STEM-EDX line analysis uses, for example, a STEM device (HD-2700 manufactured by Hitachi High-Technologies Corporation), and as an EDX detector, an Octane T Ultra W manufactured by EDAX Corporation (two are provided). When performing EDX line analysis, the shallow depth and less concave and convex part of the thinned sample is measured while setting the emission current of the STEM device to 6 μA or more and 10 μA or less. The magnification is, for example, about 150,000 times. The conditions for EDX line analysis are as follows: there is drift correction; the line width is 42 nm; the pitch is 0.2 nm; and the number of frames is six or more.

[0167] When the positive electrode active material 100 of one embodiment of the present invention is subjected to EDX surface analysis or EDX point analysis, the average detected amount of each additional element, especially the additional element X, is preferably higher in the surface layer portion 100 a than in the inner portion 100 b .

[0168] <Additional Features>

[0169] In addition, a coating portion may be attached to at least a portion of the surface of the positive electrode active material 100 . Figure 5A and Figure 5B An example of the positive electrode active material 100 to which the coating portion 104 is attached is shown.

[0170] The covering portion 104 is preferably formed by, for example, depositing electrolyte and decomposition products of the organic electrolyte during charge and discharge. x When charging is repeated in a manner in which x in MO2 becomes smaller, by including a covering portion derived from the electrolyte on the surface of the positive electrode active material 100, it is expected that the charge and discharge cycle characteristics will be improved. This is because: the increase in impedance on the surface of the positive electrode active material is suppressed; or the precipitation of cobalt is suppressed, etc. The covering portion 104 preferably contains carbon, oxygen and fluorine, for example. Furthermore, it is easy to obtain a high-quality covering portion when LiBOB and / or SUN (Suberonitrile) is used as an electrolyte. Therefore, sometimes, the quality of the covering portion 104 containing one or more selected from boron, nitrogen, sulfur and fluorine is high, so it is preferred. In addition, the covering portion 104 does not need to cover the entire positive electrode active material 100. For example, as long as more than 50% of the surface of the positive electrode active material 100 is covered, it is preferably more than 70%, and more preferably more than 90%.

[0171] This embodiment mode can be used in combination with other embodiment modes.

[0172] (Implementation Method 2) In this embodiment, an example of a method for producing the positive electrode active material 100 according to one embodiment of the present invention is described.

[0173] <<Method 1 for producing positive electrode active material>> Reference Figure 4A A method 1 for producing the positive electrode active material 100 will be described.

[0174] <Step S11> exist Figure 4A In step S11 shown in the figure, as starting materials of lithium and transition metal materials, a lithium source (Li source), a cobalt source (Co source) and a nickel source (Ni source) are prepared respectively.

[0175] The ratio of nickel to the sum of cobalt and nickel is Ni / (Co+Ni), that is, LiCo 1-y Ni y The y in O2 is preferably higher than 0.001 and lower than 0.5, and more preferably higher than 0.025 and lower than 0.215.

[0176] As the lithium source, a compound containing lithium is preferably used, for example, lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. The purity of the lithium source is preferably high, for example, a material with a purity of 99.99% or more is preferably used.

[0177] As the cobalt source, a compound containing cobalt is preferably used, and for example, cobalt oxide, cobalt hydroxide, etc. can be used.

[0178] As the nickel source, a compound containing nickel is preferably used, and for example, nickel oxide, nickel hydroxide, etc. can be used.

[0179] The purity of the cobalt source and the nickel source is preferably high, for example, preferably a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and further preferably 5N (99.999%) or more. By using high-purity materials, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is improved and / or the reliability of the secondary battery is improved.

[0180] <Step S12> Then, as Figure 4A In step S12 shown, a lithium source, a cobalt source and a nickel source are crushed and mixed to produce a mixed material. The crushing and mixing can be performed by a dry method or a wet method. The wet method is preferred because the particles can be crushed into smaller pieces and mixed. When the wet method is used, a solvent is prepared. As a solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is preferred to use a non-protonic solvent that does not react easily with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. Preferably, the lithium source and the cobalt source are mixed with dehydrated acetone with a moisture content suppressed to less than 10 ppm and a purity of 99.5% or more for crushing and mixing. By using dehydrated acetone of the above purity, impurities that may be mixed in can be reduced.

[0181] As a means for crushing and mixing, a ball mill or a sand mill can be used. When using a ball mill, alumina balls or zirconia balls are preferably used as the crushing medium. Zirconia balls are preferred because they have less impurities discharged. In addition, when using a ball mill or a sand mill, in order to suppress contamination from the medium, the circumferential speed is preferably set to 100 mm / s or more and 2000 mm / s or less. In the present embodiment, the circumferential speed is preferably set to 628 mm / s (the number of rotations is 300 rpm, and the diameter of the ball mill is 40 mm) for crushing and mixing.

[0182] <Step S13> Then, as Figure 4A In step S13 shown, the mixed material is heated. The heating is preferably performed at a temperature of 800°C or higher and 1100°C or lower, more preferably 900°C or higher and 1000°C or lower, and further preferably about 950°C. When the temperature is too low, there is a concern that the decomposition and melting of the lithium source and the cobalt source are insufficient. On the other hand, when the temperature is too high, defects may occur due to the following reasons: lithium evaporates from the lithium source; and / or the transition metal M is excessively reduced; etc. For example, cobalt and / or nickel changes from trivalent to divalent, causing oxygen defects, etc.

[0183] If the heating time is too short, lithium cobalt nickel oxide is not synthesized, but if the heating time is too long, productivity decreases. For example, the heating time is preferably 1 hour to 100 hours, more preferably 2 hours to 20 hours.

[0184] Although it varies depending on the temperature to be reached during heating, the heating rate is preferably 80° C. / h or more and 250° C. / h or less. For example, when heating at 1000° C. for 10 hours, the heating rate is preferably 200° C. / h.

[0185] The heating is preferably performed in an atmosphere with less water such as dry air, for example, preferably in an atmosphere with a dew point of -50°C or less, more preferably in an atmosphere with a dew point of -80°C or less. In the present embodiment, the heating is performed in an atmosphere with a dew point of -93°C. In addition, in order to suppress impurities that may be mixed into the material, the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere are preferably all below 5 ppb (parts per billion).

[0186] As the heating atmosphere, an oxygen-containing atmosphere is preferably used. For example, a method of continuously introducing dry air into the reaction chamber can be cited. In this case, the flow rate of the dry air is preferably 10 L / min. A method of continuously introducing oxygen into the reaction chamber so that the oxygen flows through the reaction chamber is called flowing.

[0187] When an oxygen-containing atmosphere is used as the heating atmosphere, a non-flowing method may also be used. For example, a method may be used in which the reaction chamber is first depressurized and then filled with oxygen (it may also be called purging) to prevent the oxygen from leaking from the reaction chamber or entering the reaction chamber. For example, the reaction chamber may be depressurized to -970 hPa and then continuously filled with oxygen until the pressure reaches 50 hPa.

[0188] After heating, the mixture may be cooled naturally, and the cooling time from the specified temperature to room temperature is preferably in the range of 10 hours to 50 hours. Note that it is not necessarily necessary to cool to room temperature, but only to a temperature allowed by the next step.

[0189] In this embodiment, the heating temperature is set to 900° C., the heating conditions are set to 10 hours, the heating atmosphere is set to dry air at a flow rate of 10 L / min, and the heating rate is set to 200° C. / h.

[0190] The heating in this step can be performed using a rotary kiln or a roller hearth kiln. Heating using a continuous or batch-type rotary kiln can be performed while stirring.

[0191] The crucible used for heating is preferably an alumina crucible. The alumina crucible is made of a material that does not easily release impurities. In this embodiment, a 99.9% pure alumina crucible is used. It is preferred to cover the crucible with a lid when heating. This can prevent the volatilization of the material.

[0192] In addition, compared with a new crucible, it is preferred to use a crucible that has been used many times. In this specification, etc., a new crucible refers to a crucible that has been heated by placing a material containing lithium, a transition metal M and / or an additive element twice or less. In addition, a crucible that has been used many times refers to a crucible that has been heated by placing a material containing lithium, a transition metal M and / or an additive element three or more times. This is because: when using a new crucible, there is a concern that a part of the material such as lithium fluoride is absorbed or diffused, moved and / or attached to the sagger during heating. As a result, when a part of the material is lost due to the above reasons, the concern that the element distribution of the surface layer of the positive active material is not in a suitable range increases. On the other hand, there is no such concern for a crucible that has been used many times.

[0193] After the heating is completed, it can also be crushed and screened as needed. When recovering the heated material, it can also be moved from the crucible to the mortar first, and then the heated material can be recovered. In addition, the mortar is preferably made of agate or partially stabilized zirconia. The agate or partially stabilized zirconia mortar uses a material that does not easily release impurities. Specifically, a mortar of agate or partially stabilized zirconia with a purity of more than 90%, preferably more than 99%, is used. In addition, the same heating conditions as step S13 can be used in the heating process described later other than step S13.

[0194] <Step S14> Through the above steps, it is possible to synthesize Figure 4A The lithium cobalt nickel oxide (LiCo 1-y Ni y O2).

[0195] <<Method for producing positive electrode active material 2>> Next, refer to Figure 4B and Figure 4C A method for producing a positive electrode active material 2 different from the method for producing a positive electrode active material 1 in one embodiment of the present invention is described. The difference between the method for producing a positive electrode active material 2 and the method for producing a positive electrode active material 1 is the presence or absence of an additive element. By adding the additive element, the surface of the positive electrode active material can be chemically stabilized, and the degradation of the crystal structure during the charge and discharge cycle can be suppressed. For other descriptions, the description of the production method 1 can be referred to.

[0196] The additive element may be mixed with the lithium source, the cobalt source, and the nickel source at the same time, but it is more preferable to perform the heat treatment after synthesizing lithium cobalt nickel oxide not containing the additive element and then mixing the additive element source.

[0197] In the method of synthesizing lithium cobalt nickel oxide containing an additive element by simultaneously mixing a lithium source, a cobalt source, and a nickel source with an additive element source, it is difficult to increase the concentration of the additive element in the surface portion 100a. In addition, if the additive element source is only mixed without heating after synthesizing the lithium cobalt nickel oxide, the additive element only adheres to the lithium cobalt nickel oxide and does not dissolve in the lithium cobalt nickel oxide. Unless it is fully heated, it is not easy to distribute the additive element well. Therefore, it is preferred to mix the additive element source after synthesizing the lithium cobalt nickel oxide and perform heat treatment. Sometimes the heat treatment after the above-mentioned mixing of the additive element source is called annealing.

[0198] However, when the annealing temperature is too high, cation mixing occurs and the possibility of added elements such as magnesium entering the transition metal M position increases. Furthermore, when the heat treatment temperature is too high, there is a concern of negative effects such as cobalt and nickel being reduced to divalent and lithium evaporation occurring.

[0199] Therefore, it is preferred to mix the material used as a flux (also called a flux) with the additive element source. As long as its melting point is lower than that of lithium cobalt nickel oxide, it can be said to be a material used as a flux. For example, fluorine compounds such as lithium fluoride are preferred. By adding a flux, the melting points of the additive element source and lithium cobalt nickel oxide are lowered. By lowering the melting point, it is easy to distribute the additive element well at a temperature where cation mixing is not likely to occur.

[0200] When the fluoride contains LiF and MgF2, according to Non-Patent Document 13, the eutectic point of LiF and MgF2 is about 742°C, so it is preferred to set the heating temperature to 742°C or higher in the heating step after mixing the added elements.

[0201] <Step S11 to Step S14> First, similarly to the method 1 for producing a positive electrode active material, lithium cobalt nickel oxide is synthesized through steps S11 to S14 .

[0202] <Step S20> Then, if Figure 4C As shown in step S20, an additive element A for lithium cobalt nickel oxide is prepared. While preparing the additive element source (A source), a lithium source can also be prepared.

[0203] The additional elements described in the above embodiment can be used as the additional element A. Specifically, one or two or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper, and gallium can be used. Figure 4C An example in which magnesium and fluorine are selected as the additive element A is shown.

[0204] When magnesium is selected as the additive element, the additive element source may be referred to as a magnesium source. As the magnesium source, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. may be used. In addition, a plurality of the above magnesium sources may be used.

[0205] When fluorine is selected as an additive element, the additive element source may be referred to as a fluorine source (F source). As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3) or sodium aluminum hexafluoride (Na3AlF6) may be used. Among them, lithium fluoride has a relatively low melting point of 848°C and is easily melted in the heating process described later, so it is preferred.

[0206] Magnesium fluoride can be used as both a fluorine source and a magnesium source. In addition, lithium fluoride can be used as a lithium source. As another lithium source used in step S21, there is lithium carbonate.

[0207] In addition, the fluorine source may be a gas, and fluorine (F2), carbon fluoride, sulfur fluoride or oxyfluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F) or the like may be mixed in the atmosphere in the heating step described later. In addition, a plurality of the above fluorine sources may be used.

[0208] In the present embodiment, lithium fluoride (LiF) is prepared as a fluorine source, and magnesium fluoride (MgF2) is prepared as a fluorine source and a magnesium source. When lithium fluoride and magnesium fluoride are mixed at a molar ratio of about LiF:MgF2=65:35, it is most effective in lowering the melting point. On the other hand, when there is more lithium fluoride, there is too much lithium and the cycle characteristics may be deteriorated. For this reason, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≤x≤1.9), more preferably LiF:MgF2=x:1 (0.1≤x≤0.5), and further preferably LiF:MgF2=x:1 (near x=0.33). In addition, in this specification, etc., near refers to a value greater than 0.9 times and less than 1.1 times its value.

[0209] <Step S22> Then, in Figure 4C In step S22 shown, the magnesium source and the fluorine source are pulverized and mixed. This step can be performed by selecting the pulverization and mixing conditions described in step S12.

[0210] <Step S23> Then, in Figure 4B In step S23, the pulverized and mixed materials are collected to obtain a source of the additive element A (source A). In addition, the source of the additive element A shown in step S23 includes a plurality of starting materials and can be called a mixture.

[0211] The D50 (median particle size) of the particle size of the above mixture is preferably 600 nm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less. The D50 (median particle size) when using one material as an additive element source is also preferably 600 nm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less.

[0212] When the above-mentioned micronized mixture (including the case where there is only one additive element) is used, it is easy to uniformly adhere the mixture to the surface of the lithium cobalt nickel oxide particles when mixed with lithium cobalt nickel oxide in the subsequent process. When the mixture is uniformly attached to the surface of the lithium cobalt nickel oxide particles, it is easy to uniformly distribute or diffuse the additive element in the surface layer portion 100a of the composite oxide after heating, so it is preferred.

[0213] <Step S31> Then, in Figure 4B In step S31, lithium cobalt nickel oxide and additive element source A source (A source) are mixed. The ratio of the sum of the atomic numbers M of cobalt and nickel in lithium cobalt nickel oxide to the atomic number Mg of magnesium in additive element source A is preferably M:Mg=100:y (0.1≤y≤6), and more preferably M:Mg=100:y (0.3≤y≤3).

[0214] In order not to damage the shape of the lithium cobalt nickel oxide particles, the mixing of step S31 is preferably performed under milder conditions than the mixing of step S12. For example, it is preferably performed under conditions with fewer rotations or shorter time than the mixing of step S12. In addition, the dry method is a milder condition than the wet method. For example, a ball mill, a sand mill, etc. can be used for mixing. When a ball mill is used, for example, zirconia balls are preferably used as the medium.

[0215] In the present embodiment, the mixing is performed by a dry method at 150 rpm for 1 hour using a ball mill using zirconia balls having a diameter of 1 mm. The mixing is performed in a dry room having a dew point of -100°C or higher and -10°C or lower.

[0216] <Step S32> Then, in Figure 4B In step S32, the mixed materials are recovered to obtain a mixture 903. When recovered, the materials may be sieved after being crushed as needed.

[0217] <Step S33> Then, in Figure 4B In step S33 shown, the mixture 903 is heated. The heating conditions described in step S13 can be selected and implemented. The heating time is preferably more than 2 hours. At this time, in order to increase the oxygen partial pressure of the heating atmosphere, the pressure in the furnace can also be greater than the atmospheric pressure. This is because: when the oxygen partial pressure of the heating atmosphere is insufficient, cobalt and nickel are reduced, and lithium cobalt nickel oxide and the like may not be able to maintain a layered rock salt type crystal structure.

[0218] Here, the heating temperature is supplemented. The lower limit of the heating temperature in step S33 needs to be above the temperature at which the reaction of lithium cobalt nickel oxide and the additive element source progresses. As long as the temperature at which the reaction progresses is set to a temperature at which mutual diffusion of the elements contained in the lithium cobalt nickel oxide and the additive element source occurs, it can also be lower than the melting temperature of the above-mentioned material. Taking oxide as an example, it is known that from the melting temperature T m 0.757 times (Taman temperature T d ) solid phase diffusion occurs. Therefore, the heating temperature in step S33 can be set to 650°C or above.

[0219] Of course, the reaction is more likely to proceed when the temperature is set above the temperature at which one or more of the materials selected from the mixture 903 are melted. For example, when LiF and MgF2 are included as the additive element source, the eutectic point of LiF and MgF2 is around 742°C, so the lower limit of the heating temperature in step S33 is preferably set to 742°C or above.

[0220] In addition, in the mixture 903 obtained by mixing LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio), an endothermic peak was observed at around 830° C. in differential scanning calorimetry (DSC measurement). Therefore, the lower limit of the heating temperature is more preferably 830° C. or higher.

[0221] As the heating temperature is higher, the reaction proceeds more easily, and thus the heating time can be shortened, thereby improving productivity, which is preferred.

[0222] The upper limit of the heating temperature is set to be lower than the decomposition temperature of the lithium cobalt nickel oxide. At a temperature near the decomposition temperature, slight decomposition of the lithium cobalt nickel oxide may occur. Therefore, the upper limit of the heating temperature is more preferably 1000°C or lower, further preferably 950°C or lower, and further preferably 900°C or lower.

[0223] In summary, the heating temperature in step S33 is preferably 650°C or higher and 1130°C or lower, more preferably 650°C or higher and 1000°C or lower, further preferably 650°C or higher and 950°C or lower, and further preferably 650°C or higher and 900°C or lower. In addition, it is preferably 742°C or higher and 1130°C or lower, more preferably 742°C or higher and 1000°C or lower, further preferably 742°C or higher and 950°C or lower, and further preferably 742°C or higher and 900°C or lower. In addition, it is preferably 800°C or higher and 1100°C or lower, more preferably 830°C or higher and 1130°C or lower, further preferably 830°C or higher and 1000°C or lower, further preferably 830°C or higher and 950°C or lower, and further preferably 830°C or higher and 900°C or lower.

[0224] When the mixture 903 is heated, the partial pressure of fluorine or fluoride derived from the fluorine source or the like is preferably controlled within an appropriate range.

[0225] In the manufacturing method described in this embodiment, some materials such as LiF as a fluorine source are sometimes used as a flux. Through the above function, the heating temperature can be reduced to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, above 742°C and below 950°C, and the added elements can be distributed in the surface layer, thereby manufacturing a positive electrode active material with good characteristics.

[0226] However, the specific gravity of LiF in the gas state is lighter than that of oxygen, so it is possible that LiF is volatilized by heating, and when LiF is volatilized, the LiF in the mixture 903 is reduced. At this time, the function of LiF as a flux is reduced. Therefore, it is necessary to heat while suppressing the volatilization of LiF. In addition, even if LiF is not used as a fluorine source, it is possible that Li on the surface of LiCoO2 reacts with F as a fluorine source to generate LiF and the LiF is volatilized. Therefore, even if a fluoride having a melting point higher than LiF is used, it is also necessary to suppress volatilization.

[0227] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing LiF, that is, to heat the mixture 903 in a state where the partial pressure of LiF in the heating furnace is high. By heating as described above, volatilization of LiF in the mixture 903 can be suppressed.

[0228] The heating in this step is preferably performed in a manner that does not cause the particles of the mixture 903 to adhere together. When the particles of the mixture 903 adhere together during heating, the area of ​​the particles in contact with oxygen in the atmosphere is reduced, and the diffusion path of the added element (such as fluorine) is blocked, so that the added element (such as magnesium and fluorine) may not be easily distributed in the surface layer.

[0229] In addition, it can be considered that when adding elements (such as fluorine) uniformly distributed in the surface layer, a smooth and less concavoconvex positive electrode active material can be obtained. Therefore, in order to maintain the state of the surface smoothness of the heating through step S15 or further make the surface smooth in this process, it is preferred that the mixture 903 particles are not bonded together.

[0230] In addition, when heating is performed using a rotary kiln, it is preferred to control the flow rate of the oxygen-containing atmosphere in the kiln for heating. For example, it is preferred to reduce the flow rate of the oxygen-containing atmosphere; first purge the atmosphere to introduce the oxygen atmosphere into the kiln, and then stop the atmosphere from flowing; etc. When the oxygen is flowing, the fluorine source may evaporate, which is not preferred in order to maintain the smoothness of the surface.

[0231] When heating is performed using a roller kiln, for example, by covering the container containing the mixture 903 with a lid, the mixture 903 can be heated in a LiF-containing atmosphere.

[0232] Supplementary description of the heating time. The heating time varies depending on the heating temperature, the size of the lithium cobalt nickel oxide in step S14, the composition, etc. When the lithium cobalt nickel oxide is small, it is sometimes more preferable to heat at a lower temperature or for a shorter time than when the lithium cobalt nickel oxide is large.

[0233] In addition, Figure 4B and Figure 4C The manufacturing method of heating after mixing and adding the element A source is described in the above, but one embodiment of the present invention is not limited to this. In addition, the heating of step S33 can also be performed without mixing and adding the element A source. By heating the lithium cobalt nickel oxide of step S14 in step S33, it is expected that the crystallinity of the lithium cobalt nickel oxide will be improved. In addition, it is also expected that the skewness and misalignment caused by the shrinkage difference of the lithium cobalt nickel oxide can be suppressed.

[0234] <Step S34> Then, in Figure 4B In step S34 shown, the heated material is recovered and ground as needed to obtain the positive electrode active material 100. At this time, it is preferred that the recovered particles are also screened. Through the above steps, the positive electrode active material 100 of one embodiment of the present invention can be manufactured. The surface of the positive electrode active material of one embodiment of the present invention is smooth.

[0235] This embodiment mode can be used in combination with other embodiment modes.

[0236] (Implementation method 3) In this embodiment, refer to Figure 6 7 and 7 illustrate an example of a secondary battery according to one embodiment of the present invention.

[0237] <Structural Example of Secondary Battery> The following uses Figure 6 a secondary battery in which the positive electrode, negative electrode, and electrolyte shown are surrounded by an outer packaging body as an example for explanation.

[0238] 〔Positive Electrode〕 The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and may also contain a conductive material (synonymous with a conductive additive) and a binder. The positive electrode active material described in the above-described embodiment is used as the positive electrode active material.

[0239] In addition, the positive electrode active material described in the above-described embodiment and other positive electrode active materials may be mixed and used.

[0240] Examples of other positive electrode active materials include composite oxides having an olivine-type crystal structure, a layered rock salt-type crystal structure, or a spinel-type crystal structure. For example, compounds such as LiFePO4, LiFeO2, LiNiO2, LiMn2O4, V2O5, Cr2O5, and MnO2 can be cited.

[0241] In addition, as other positive electrode active materials, it is preferable to mix lithium nickelate (LiNiO2 or LiNi 1-x M x O2 (0 < x < 1) (M = Co, Al, etc.)) with a lithium-containing material having a spinel-type crystal structure containing manganese such as LiMn2O4. By adopting this structure, the characteristics of the secondary battery can be improved.

[0242] As the conductive material, carbon materials such as acetylene black can be used. In addition, as the conductive material, carbon nanotubes, graphene, or graphene compounds can be used.

[0243] Graphene compounds in this specification and the like include multi-layer graphene, multi-graphene, graphene oxide, multi-layer graphene oxide, multi-oxide graphene, reduced graphene oxide, reduced multi-layer graphene oxide, reduced multi-oxide graphene, graphene quantum dots, etc. A graphene compound refers to a compound containing carbon and having a two-dimensional structure formed by carbon six-membered rings in a flat plate shape, sheet shape, etc. In addition, the two-dimensional structure formed by carbon six-membered rings is sometimes referred to as a carbon sheet. A graphene compound may also have a functional group. In addition, a graphene compound preferably has a curved shape. In addition, a graphene compound may be curled like a carbon nanofiber.

[0244] In this specification and the like, graphene oxide refers to a graphene compound containing carbon and oxygen, having a sheet shape, and including a functional group, especially including an epoxy group, a carboxyl group, or a hydroxyl group.

[0245] In this specification, etc., reduced graphene oxide refers to a compound containing carbon and oxygen, having a sheet shape and having a two-dimensional structure formed by a carbon six-membered ring. One layer of reduced graphene oxide can function, but a stacked structure can also be used. The reduced graphene oxide preferably has a portion with a carbon concentration greater than 80 atomic% and an oxygen concentration of 2 atomic% or more and 15 atomic% or less. By having this carbon concentration and oxygen concentration, a small amount of reduced graphene oxide can also have the function of a conductive material with high conductivity. In addition, it is preferred that the intensity ratio G / D of the G band to the D band of the Raman spectrum of the reduced graphene oxide is greater than 1. Reduced graphene oxide having this intensity ratio can have the function of a conductive material with high conductivity even in a small amount.

[0246] Graphene compounds sometimes have excellent electrical properties such as high conductivity and excellent physical properties such as high flexibility and high mechanical strength. In addition, graphene compounds have a flaky shape. Graphene compounds sometimes have a curved surface, which can achieve surface contact with low contact resistance. Graphene compounds sometimes have very high conductivity even if their thickness is thin, so a conductive path can be formed in the active material layer with a small amount and high efficiency. Thus, by using graphene compounds as conductive materials, the contact area between the active material and the conductive material can be increased. The graphene compound preferably covers more than 80% of the area of ​​the active material. Note that it is preferred that the graphene compound clings to at least a portion of the active material particles. It is preferred that the graphene compound overlaps at least a portion of the active material particles. It is preferred that the shape of the graphene compound is consistent with at least a portion of the shape of the active material particles. The shape of the active material particle refers to the concave-convex such as a single active material particle or the concave-convex formed by a plurality of active material particles. It is preferred that the graphene compound surrounds at least a portion of the active material particle. The graphene compound may have holes.

[0247] When using active material particles with a small particle size, for example, when using active material particles with a particle size of 1 μm or less, the specific surface area of ​​the active material particles is large, so more conductive paths connecting the active material particles are required. In this case, it is preferred to use a graphene compound that can efficiently form a conductive path even in a small amount.

[0248] Due to the above properties, it is particularly effective to use graphene compounds as conductive materials for secondary batteries that require rapid charging and rapid discharging. For example, two-wheeled or four-wheeled vehicle-mounted secondary batteries, secondary batteries for drones, etc. sometimes need to have rapid charging and rapid discharging characteristics. Mobile electronic devices, etc. sometimes also need to have rapid charging characteristics. Rapid charging and discharging, for example, refers to charging and discharging of 200mA / g, 400mA / g or 1000mA / g or more.

[0249] Since the plurality of graphenes or graphene compounds are formed so as to cover a part of the plurality of positive electrode active material particles or adhere to the surfaces of the plurality of positive electrode active material particles, the plurality of graphenes or graphene compounds are preferably in surface contact with the plurality of positive electrode active material particles.

[0250] Here, by making a plurality of graphenes or graphene compounds bonded to each other, a meshed graphene compound sheet (hereinafter referred to as a graphene compound net or a graphene net) can be formed. When the graphene net covers the active material, the graphene net can be used as an adhesive for bonding the active materials to each other. Therefore, the amount of the adhesive can be reduced or the adhesive can be omitted, thereby increasing the ratio of the active material in the electrode volume and the electrode weight. In other words, the discharge capacity of the secondary battery can be increased.

[0251] In addition, in addition to the graphene compound, a material used in forming the graphene compound may be mixed and used in the active material layer. For example, particles used as a catalyst in forming the graphene compound and the graphene compound may be mixed. As catalysts in forming the graphene compound, for example, silicon oxide (SiO2, SiO x (x<2)), particles of aluminum oxide, iron, nickel, ruthenium, iridium, platinum, copper, germanium, etc. The median particle size (D50) of the particles is preferably 1 μm or less, more preferably 100 nm or less.

[0252] [Adhesive] As the adhesive, for example, preferably used are rubber materials such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Fluorine rubber can also be used as the adhesive.

[0253] In addition, as a binder, for example, a water-soluble polymer is preferably used. As a water-soluble polymer, for example, polysaccharides can also be used. As polysaccharides, one or more of cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, and starch can be used. It is more preferred to use these water-soluble polymers and the above-mentioned rubber material in combination.

[0254] Alternatively, as an adhesive, it is preferred to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose.

[0255] As the binder, a plurality of the above-mentioned materials may be used in combination.

[0256] [current collector] As the current collector, materials with high conductivity such as stainless steel, gold, platinum, aluminum, titanium and other metals and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum, etc. that improve heat resistance are added can be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. As the current collector, shapes such as foil, plate, sheet, mesh, punched metal mesh, and drawn metal mesh can be appropriately used. The thickness of the current collector is preferably 5 μm or more and 30 μm or less.

[0257] 〔negative electrode〕 The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may also include a conductive material and a binder.

[0258] [Negative electrode active material] As the negative electrode active material, for example, an alloy material and / or a carbon material can be used.

[0259] As the negative electrode active material, an element that can perform a charge and discharge reaction by alloying / de-alloying reaction with lithium can be used. For example, a material containing one or more selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The charge and discharge capacity of this element is larger than that of carbon, and in particular, the theoretical capacity of silicon is large, which is 4200mAh / g. Therefore, silicon is preferably used for the negative electrode active material. In addition, compounds containing these elements can also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb and SbSn can be cited. Elements that can undergo charge and discharge reactions through alloying / de-alloying reactions with lithium, compounds containing the elements, and the like are sometimes referred to as alloy-based materials.

[0260] In this specification, SiO refers to silicon monoxide, for example. Alternatively, SiO may also be represented as SiO x Here, x preferably represents a value near 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less. Alternatively, x is preferably 0.2 or more and 1.2 or less. Alternatively, x is preferably 0.3 or more and 1.5 or less.

[0261] As the carbon-based material, graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon nanotube, graphene, carbon black, and the like can be used.

[0262] As graphite, artificial graphite or natural graphite can be cited. As artificial graphite, for example, mesocarbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. can be cited. Here, spherical graphite with a spherical shape can be used as artificial graphite. For example, MCMB sometimes has a spherical shape, so it is preferred. In addition, MCMB is relatively easy to reduce its surface area, so it is sometimes preferred. As natural graphite, for example, flaky graphite, spheroidized natural graphite, etc. can be cited.

[0263] When lithium ions are intercalated in graphite (when lithium-graphite intercalation compounds are generated), graphite shows a potential as low as that of lithium metal (0.05 V or more and 0.3 V or less vs. Li / Li + ). As a result, lithium-ion secondary batteries can show high operating voltages. Graphite also has the following advantages: large charge and discharge capacity per unit volume; relatively small volume expansion; low cost; and higher safety than lithium metal, so it is preferred.

[0264] In addition, as the negative electrode active material, oxides such as titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten dioxide (WO2), molybdenum dioxide (MoO2), etc.

[0265] In addition, as the negative electrode active material, Li 3 N type structure containing lithium and transition metal nitride can be used. 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N3 shows large charge and discharge capacity (900mAh / g, 1890mAh / cm 3 ), so it is preferred.

[0266] When a nitride containing lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, so it can be combined with a material that does not contain lithium ions, such as V2O5 and Cr3O8, which is used as a positive electrode active material, and is therefore preferred. Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal can also be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0267] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. Materials that cause conversion reactions can also include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, CoS 0.89 , sulfides such as NiS, CuS, nitrides such as Zn3N2, Cu3N, Ge3N4, phosphides such as NiP2, FeP2, CoP3, fluorine compounds such as FeF3, BiF3.

[0268] As the conductive material and the binder which may be contained in the negative electrode active material layer, the same conductive material and the binder which may be contained in the positive electrode active material layer may be used.

[0269] [Negative electrode current collector] As the negative electrode current collector, the same material as the positive electrode current collector can be used. In addition, as the negative electrode current collector, it is preferable to use a material that does not alloy with carrier ions such as lithium.

[0270] 〔Electrolyte〕 The electrolyte includes a solvent and a dielectric. As the solvent of the electrolyte, an aprotic organic solvent is preferably used, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme (methyl diglyme), acetonitrile, benzonitrile, tetrahydrofuran, cyclopentane sulfone, sultone, etc., or two or more of the above can be used in any combination and ratio.

[0271] In addition, by using one or more ionic liquids (room temperature molten salts) with flame retardancy and low volatility as the solvent of the electrolyte, even if the internal temperature rises due to the internal short circuit or overcharge of the secondary battery, the rupture and / or ignition of the secondary battery can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As the organic cations for the electrolyte, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as the anions for the electrolyte, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0272] In addition, as the electrolyte solution dissolved in the above solvent, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2 and other lithium salts, or two or more of the above can be used in any combination and ratio.

[0273] As the electrolyte for the secondary battery, it is preferred to use a highly purified electrolyte with a low content of granular dust or elements other than the constituent elements of the electrolyte (hereinafter referred to as "impurities"). Specifically, the ratio of impurities to the weight of the electrolyte is less than 1%, preferably less than 0.1%, and more preferably less than 0.01%.

[0274] In addition, additives such as vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate borate) (LiBOB) or dinitrile compounds such as succinonitrile and adiponitrile, fluorobenzene, and ethylene glycol bis(propionitrile) ether may be added to the electrolyte. The concentration of the added materials may be set to, for example, 0.1 wt% or more and 5 wt% or less in the entire solvent. VC or LiBOB is particularly preferred because it is easy to form a good covering portion.

[0275] Alternatively, a polymer gel electrolyte in which a polymer is swollen with an electrolyte solution may be used.

[0276] By using a polymer gel electrolyte, safety against leakage can be improved, and the secondary battery can be made thinner and lighter.

[0277] As the gelled polymer, silicone gel, acrylic acid gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, fluorine polymer gel, etc. can be used.

[0278] As the polymer, for example, a polymer having a polyoxyalkylene structure such as polyethylene oxide (PEO), PVDF and polyacrylonitrile, and copolymers containing these can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. In addition, the formed polymer can also have a porous shape.

[0279] In addition, solid electrolytes containing inorganic materials such as sulfides or oxides, solid electrolytes containing polymer materials such as PEO (polyethylene oxide), etc. can be used instead of electrolytes. When a solid electrolyte is used, it is not necessary to set a separator and / or a spacer. In addition, since the entire battery can be solidified, there is no worry about leakage and safety is significantly improved.

[0280] 〔Isolated Body〕 The secondary battery preferably includes a separator. As the separator, for example, the following materials can be used: paper, non-woven fabric, glass fiber, ceramic, or synthetic fibers including nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic resin, polyolefin, polyurethane, etc. The separator is preferably processed into a bag shape and arranged in a manner to surround either the positive electrode or the negative electrode.

[0281] The separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon or aromatic polyamide (meta-aramid or para-aramid) may be used.

[0282] By coating ceramic materials, the oxidation resistance is improved, thereby suppressing the degradation of the separator caused by high-voltage charging and discharging, thereby improving the reliability of the secondary battery. By coating fluorine materials, it is easy to make the separator close to the electrode, which can improve the output characteristics. By coating polyamide materials, especially aromatic polyamide, the heat resistance is improved, thereby improving the safety of the secondary battery.

[0283] For example, a mixture of aluminum oxide and aramid may be applied to both sides of a polypropylene film. Alternatively, a mixture of aluminum oxide and aramid may be applied to the surface of the polypropylene film in contact with the positive electrode and a fluorine-based material may be applied to the surface in contact with the negative electrode.

[0284] By adopting a separator having a multi-layer structure, the safety of the secondary battery can be ensured even if the total thickness of the separator is small, and thus the discharge capacity per unit volume of the secondary battery can be increased.

[0285] 〔Outer packaging〕 As the outer packaging body included in the secondary battery, for example, metal materials such as aluminum and / or resin materials can be used. In addition, a film-shaped outer packaging body can also be used. As the film, for example, a three-layer structure film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is provided on a film composed of materials such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as a polyamide resin, polyester resin, etc. is provided on the metal film as the outer surface of the outer packaging body.

[0286] <Laminated secondary battery and method for manufacturing the same> Figure 6 FIG. 7 shows an example of an appearance diagram of a laminated secondary battery 500. Figure 6 As shown in FIG. 7 , a secondary battery 500 includes: a positive electrode 503 having a positive electrode current collector 501 and a positive electrode active material layer 502; a negative electrode 506 having a negative electrode current collector 504 and a negative electrode active material layer 505; a separator 507; an outer package 509; a positive electrode lead electrode 510; and a negative electrode lead electrode 511. When a flexible laminated secondary battery is mounted on an electronic device having at least a portion of flexibility, the secondary battery can be bent along the deformation of the electronic device. 7A to 7C An example of a method for producing the laminated secondary battery will be described.

[0287] First, the negative electrode 506, the separator 507, and the positive electrode 503 are stacked. Figure 7B The stacked negative electrode 506, separator 507, and positive electrode 503 are shown. Here, an example using 5 sets of negative electrodes and 4 sets of positive electrodes is shown. Next, the tab regions of the positive electrode 503 are joined to each other, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. As the joining, ultrasonic welding or the like can be used, for example. Similarly, the tab regions of the negative electrode 506 are joined to each other, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0288] Next, the negative electrode 506 , the separator 507 , and the positive electrode 503 are arranged on the outer package 509 .

[0289] Below, as Figure 7C As shown, the outer package 509 is folded along the portion indicated by the dotted line. Then, the outer periphery of the outer package 509 is joined. As the joining method, for example, heat pressing or the like can be used. At this time, in order to inject the electrolyte later, a non-joined area (hereinafter referred to as the introduction port) is provided on a part (or one side) of the outer package 509.

[0290] Next, an electrolyte (not shown) is introduced into the inner side of the outer packaging body 509 from an introduction port provided in the outer packaging body 509. The electrolyte is preferably introduced under a reduced pressure atmosphere or an inert gas atmosphere. Finally, the introduction port is joined. In this way, the laminated secondary battery 500 can be manufactured.

[0291] By using the positive electrode active material described in the above embodiment for the positive electrode 503 , it is possible to realize the secondary battery 500 having a high discharge capacity and excellent cycle characteristics.

[0292] This embodiment mode can be used in combination with other embodiment modes as appropriate.

[0293] (Implementation 4) In this embodiment, refer to FIG. 8A to FIG. 8C An example in which the secondary battery of one embodiment of the present invention is incorporated in an electronic device will be described.

[0294] FIG. 8A to FIG. 8G An example of installing the secondary battery with a positive electrode active material described in the above embodiment in an electronic device is shown. As electronic devices using secondary batteries, for example, television sets (also called televisions or television receivers), displays for computers, etc., digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones, mobile phone devices), portable game consoles, portable information terminals, sound reproduction devices, large game consoles such as pinball machines, etc. can be cited.

[0295] Furthermore, the flexible secondary battery can be assembled along the curved surface of the inner wall or outer wall of a house or a building, or the interior or exterior of a car.

[0296] Fig. 8A An example of a mobile phone is shown. The mobile phone 7400 includes an operation button 7403, an external connection port 7404, a speaker 7405, a microphone 7406, and the like in addition to a display portion 7402 assembled in a housing 7401. In addition, the mobile phone 7400 includes a secondary battery 7407. By using a secondary battery of one embodiment of the present invention as the secondary battery 7407, a mobile phone that is lightweight and has a long service life can be provided.

[0297] Figure 8B The figure shows a state where the mobile phone 7400 is bent. When the mobile phone 7400 is deformed by an external force and the entirety of the mobile phone 7400 is bent, the secondary battery 7407 provided inside the mobile phone 7400 is also bent. Figure 8C The state of the secondary battery 7407 being bent at this time is shown. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is fixed in a bent state. The secondary battery 7407 has a lead electrode electrically connected to a current collector. For example, the current collector is a copper foil, a part of which is alloyed with gallium to improve the adhesion with the active material layer in contact with the current collector, so that the reliability of the secondary battery 7407 in a bent state is improved.

[0298] Fig.8D An example of a bracelet-type display device is shown. A portable display device 7100 includes a housing 7101, a display portion 7102, operation buttons 7103, and a secondary battery 7104. Fig. 8E A bent secondary battery 7104 is shown. When the bent secondary battery 7104 is put on the user's arm, the frame of the secondary battery 7104 is deformed, so that the curvature of part or all of the secondary battery 7104 changes. The value representing the degree of curvature of any point of the curve by the value of the equivalent circle radius is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, part or all of the main surface of the frame or the secondary battery 7104 is deformed in a range where the radius of curvature is greater than 40 mm and less than 150 mm. As long as the radius of curvature in the main surface of the secondary battery 7104 is within the range of greater than 40 mm and less than 150 mm, high reliability can be maintained. By using a secondary battery of one embodiment of the present invention as the above-mentioned secondary battery 7104, a portable display device that is lightweight and has a long service life can be provided.

[0299] Fig.8F The portable information terminal 7200 is an example of a wristwatch-type portable information terminal. The portable information terminal 7200 includes a housing 7201, a display portion 7202, a strap 7203, a buckle 7204, operation buttons 7205, an input / output terminal 7206, and the like.

[0300] Portable information terminal 7200 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, network communication, computer games, etc.

[0301] The display surface of the display portion 7202 is curved, and display can be performed along the curved display surface. In addition, the display portion 7202 has a touch sensor, and operation can be performed by touching the screen with a finger or a stylus pen. For example, by touching an icon 7207 displayed on the display portion 7202, an application can be started.

[0302] In addition to time setting, operation button 7205 may have various functions such as power switch, wireless communication switch, setting and canceling silent mode, setting and canceling power saving mode, etc. For example, by using an operating system incorporated in portable information terminal 7200, the function of operation button 7205 can be freely set.

[0303] In addition, the portable information terminal 7200 can perform short-range wireless communication standardized by communication. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0304] In addition, the portable information terminal 7200 has an input / output terminal 7206, and can directly send data to or receive data from other information terminals through a connector. In addition, charging can also be performed through the input / output terminal 7206. In addition, the charging operation can also be performed using wireless power supply without using the input / output terminal 7206.

[0305] The display unit 7202 of the portable information terminal 7200 includes a secondary battery of one embodiment of the present invention. By using a secondary battery of one embodiment of the present invention, a portable information terminal that is lightweight and has a long service life can be provided. For example, a bent Fig. 8E The secondary battery 7104 shown is incorporated in the housing 7201 , or the secondary battery 7104 is incorporated in the belt 7203 in a bendable state.

[0306] The portable information terminal 7200 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a human body sensor such as a temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, etc. are preferably installed as the sensor.

[0307] Figure 8G An example of an armband-type display device is shown. The display device 7300 includes a display portion 7304 and a secondary battery of one embodiment of the present invention. The display device 7300 may include a touch sensor in the display portion 7304 and be used as a portable information terminal.

[0308] The display surface of the display portion 7304 is curved and can display along the curved display surface. In addition, the display device 7300 can change the display state by using short-range wireless communication or the like that has been standardized for communication.

[0309] The display device 7300 has an input / output terminal, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the input / output terminal. In addition, charging can also be performed using wireless power supply instead of using the input / output terminal.

[0310] By using the secondary battery of one embodiment of the present invention as a secondary battery included in the display device 7300 , a display device that is lightweight and has a long service life can be provided.

[0311] In addition, refer to Figure 8H 9 and 10 illustrate an example in which the secondary battery having excellent cycle characteristics described in the above embodiment is incorporated into an electronic device.

[0312] By using a secondary battery of one embodiment of the present invention as a secondary battery for daily electronic devices, a product with a light weight and a long service life can be provided. For example, as daily electronic devices, electric toothbrushes, electric shavers, electric beauty devices, etc. can be cited, and the secondary batteries in these products are expected to have a rod-like shape for easy gripping by users and be small, light, and have a high discharge capacity.

[0313] Figure 8H This is a perspective view of a device called a liquid-containing smoking device (electronic cigarette). Figure 8H In the embodiment, the electronic cigarette 7500 includes: an atomizer 7501 including a heating element; a secondary battery 7504 for supplying power to the atomizer; and a cartridge 7502 including a liquid supply container and a sensor. In order to improve safety, a protection circuit for preventing overcharging and / or overdischarging of the secondary battery 7504 may also be electrically connected to the secondary battery 7504. Figure 8H The secondary battery 7504 shown includes an external terminal for connecting to a charger. When the electronic cigarette 7500 is held, the secondary battery 7504 is located at the top, so it is preferably short in total length and light in weight. Since the secondary battery of one embodiment of the present invention has a high discharge capacity and excellent cycle characteristics, a small and lightweight electronic cigarette 7500 that can be used for a long time can be provided.

[0314] Fig.9A An example of a wearable device is shown. A secondary battery is used as a power source of the wearable device. In addition, in order to improve the splash-proof, waterproof or dust-proof performance when the user uses the wearable device in daily life or outdoors, the user not only wants the wearable device to be able to be charged by wire with the connected connector partially exposed, but also wants to be able to be charged wirelessly.

[0315] For example, the secondary battery of one embodiment of the present invention can be installed in Fig.9A The eyeglass-type device 4000 is shown. The eyeglass-type device 4000 includes a frame 4000a and a display unit 4000b. By installing a secondary battery in the temple portion of the curved frame 4000a, a light-weight, well-balanced eyeglass-type device 4000 with a long continuous use time can be realized. By using a secondary battery of one embodiment of the present invention, the required saving of the frame can be achieved.

[0316] In addition, the secondary battery of one embodiment of the present invention can be installed in the earphone type device 4001. The earphone type device 4001 includes at least a microphone part 4001a, a flexible tube 4001b, and an earphone part 4001c. In addition, a secondary battery can be provided in the flexible tube 4001b and / or in the earphone part 4001c. By using the secondary battery of one embodiment of the present invention, the saving required for the miniaturization of the frame can be achieved.

[0317] The secondary battery of one embodiment of the present invention may be mounted on a device 4002 that can be directly mounted on the body. The secondary battery 4002b may be provided in a thin housing 4002a of the device 4002. By using the secondary battery of one embodiment of the present invention, the housing can be reduced in size.

[0318] The secondary battery of one embodiment of the present invention may be mounted on the device 4003 that can be mounted on clothing. The secondary battery 4003b may be provided in the thin housing 4003a of the device 4003. By using the secondary battery of one embodiment of the present invention, it is possible to realize the saving required for miniaturization of the housing.

[0319] In addition, the secondary battery of one embodiment of the present invention can be mounted on the belt-type device 4006. The belt-type device 4006 includes a belt portion 4006a and a wireless power supply and reception portion 4006b, and the secondary battery can be mounted inside the belt portion 4006a. By using the secondary battery of one embodiment of the present invention, the required saving required for miniaturization of the housing can be achieved.

[0320] In addition, the secondary battery of one embodiment of the present invention can be mounted on the watch type device 4005. The watch type device 4005 includes a display portion 4005a and a strap portion 4005b, and the secondary battery can be set on the display portion 4005a or the strap portion 4005b. By using the secondary battery of one embodiment of the present invention, the saving required for the miniaturization of the frame can be achieved.

[0321] The display unit 4005a can display various information such as e-mails and incoming phone calls in addition to the time.

[0322] In addition, since the watch-type device 4005 is a wearable device that is directly wrapped around the wrist, it can also be equipped with sensors for measuring the user's pulse, blood pressure, etc. Thus, the user's exercise volume and health-related data can be stored for health management.

[0323] Fig. 9B A perspective view of a watch-type device 4005 is shown removed from a wrist.

[0324] in addition, Fig. 9C A side view is shown. Fig. 9C The case where a secondary battery 913 is built in is shown. The secondary battery 913 is the secondary battery described in Embodiment Mode 4. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and is small and lightweight.

[0325] Fig.9D An example of wireless earphones is shown. Here, a wireless earphone including a pair of main body 4100a and main body 4100b is shown, but the main body does not need to be a pair.

[0326] The main body 4100a and 4100b includes a driver unit 4101, an antenna 4102, and a secondary battery 4103. In addition, a display portion 4104 may be included. In addition, it is preferable to include a substrate on which a circuit such as a wireless IC is mounted, a charging terminal, etc. In addition, a microphone may be included.

[0327] The storage box 4110 includes a secondary battery 4111. In addition, it is preferable to include a substrate on which circuits such as a wireless IC and a charging control IC are mounted, and a charging terminal. In addition, a display unit, buttons, and the like may also be included.

[0328] The main bodies 4100a and 4100b can communicate with other electronic devices such as smartphones wirelessly. Therefore, the main bodies 4100a and 4100b can reproduce the sound data received from other electronic devices. In addition, when the main bodies 4100a and 4100b include microphones, the sound acquired by the microphones can be transmitted to other electronic devices for processing by the electronic devices, and then the sound data can be transmitted to the main bodies 4100a and 4100b for reproduction. Thus, for example, it can be used as a translation machine.

[0329] In addition, the secondary battery 4103 included in the main body 4100a can be charged from the secondary battery 4111 included in the storage box 4110. As the secondary battery 4111 and the secondary battery 4103, the coin-type secondary battery, the cylindrical secondary battery, etc. of the above-mentioned embodiment can be used. The secondary battery using the positive electrode active material 100 that can be obtained in the first embodiment for the positive electrode has a high energy density. By using the positive electrode active material 100 for the secondary battery 4103 and the secondary battery 4111, the energy conservation required for the miniaturization of the wireless headset can be achieved.

[0330] Fig. 10A An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the surface of a frame 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk automatically, detect garbage 6310, and can suck up garbage from the suction port set below.

[0331] For example, the sweeping robot 6300 can determine whether there are obstacles such as walls, furniture, or steps by analyzing the image taken by the camera 6303. In addition, when objects such as wiring that may be entangled with the brush 6304 are found through image analysis, the rotation of the brush 6304 can be stopped. The sweeping robot 6300 is equipped with a secondary battery 6306 and a semiconductor device or an electronic component according to one embodiment of the present invention. By using the secondary battery 6306 according to one embodiment of the present invention in the sweeping robot 6300, the sweeping robot 6300 can be made into an electronic device with a long driving time and high reliability.

[0332] Fig. 10B An example of a robot is shown. Fig. 10B The robot 6400 shown includes a secondary battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0333] The microphone 6402 has a function of sensing the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0334] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0335] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of travel when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can move safely by checking the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.

[0336] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component. By using the secondary battery according to one embodiment of the present invention in the robot 6400, the robot 6400 can be made into an electronic device with a long driving time and high reliability.

[0337] Fig. 10C An example of a flying object is shown. Fig. 10C The flying object 6500 shown includes a propeller 6501, a camera 6502, a secondary battery 6503, etc., and has an autonomous flight function.

[0338] For example, the image data captured by the camera 6502 is stored in the electronic component 6504. The electronic component 6504 can determine whether there is an obstacle during movement by analyzing the image data. In addition, the electronic component 6504 can be used to infer the remaining power of the battery from the change in the storage capacity of the secondary battery 6503. The flying body 6500 is equipped with a secondary battery 6503 according to one embodiment of the present invention. By using a secondary battery according to one embodiment of the present invention in the flying body 6500, the flying body 6500 can be made into an electronic device with a long driving time and high reliability.

[0339] This embodiment mode can be implemented in combination with other embodiment modes as appropriate.

[0340] (Implementation method 5) In this embodiment, an example in which a secondary battery having a positive electrode active material according to one embodiment of the present invention is mounted on a vehicle is described.

[0341] When a secondary battery is installed in a vehicle, a next-generation clean energy vehicle such as a hybrid vehicle (HV), an electric vehicle (EV), or a plug-in hybrid vehicle (PHV) can be realized.

[0342] FIG. 11 illustrates a vehicle using a secondary battery according to one embodiment of the present invention. Fig.11A The car 8400 shown is an electric car that uses an electric motor as a power source for traveling. Alternatively, the car 8400 is a hybrid car that can appropriately use an electric motor or an engine as a power source for traveling. By adopting one embodiment of the present invention, a vehicle with a long driving distance can be realized. In addition, the car 8400 is equipped with a secondary battery. For example, the modules of the secondary battery can be arranged in the floor portion of the vehicle. The secondary battery not only drives the electric motor 8406, but also supplies electricity to light-emitting devices such as the headlights 8401 and interior lights (not shown).

[0343] Furthermore, the secondary battery can supply electric power to a display device such as a speedometer and a tachometer included in the automobile 8400. Furthermore, the secondary battery can supply electric power to a semiconductor device such as a navigation system included in the automobile 8400.

[0344] exist Fig. 11B In the illustrated automobile 8500 , the secondary battery included in the automobile 8500 can be charged by receiving electric power from an external charging device using a plug-in method and / or a contactless power supply method. Fig. 11B The case where a secondary battery 8024 installed in a car 8500 is charged from a ground-mounted charging device 8021 through a cable 8022 is shown. When charging, the charging method and the specifications of the connector can be appropriately performed in accordance with the provisions of CHAdeMO (registered trademark) or the combined charging system "Combined Charging System". As the charging device 8021, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the secondary battery 8024 installed in the car 8500 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an ACDC converter.

[0345] In addition, although not shown, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road and / or the outer wall, charging can be performed not only when the vehicle is parked, but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between vehicles. Furthermore, solar cells can be set on the outside of the vehicle to charge the secondary battery when it is parked and / or when it is driving. Such non-contact power supply can be achieved using electromagnetic induction and / or magnetic field resonance.

[0346] Fig. 11C This is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. Fig. 11C The small motorcycle 8600 shown includes a secondary battery 8602, a rearview mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply power to the turn signal light 8603.

[0347] In addition, Fig. 11C In the illustrated scooter 8600, the secondary battery 8602 can be stored in the storage box 8604 under the seat. Even if the storage box 8604 under the seat is small, the secondary battery 8602 can be stored in the storage box 8604 under the seat. The secondary battery 8602 is detachable, so when charging, the secondary battery 8602 can be brought indoors, charged, and stored before driving.

[0348] By adopting one method of the present invention, the cycle characteristics and discharge capacity of the secondary battery can be improved. As a result, the secondary battery itself can be made small and lightweight. In addition, if the secondary battery itself can be made small and lightweight, it will help to achieve the lightweight of the vehicle, thereby extending the driving distance. In addition, the secondary battery installed in the vehicle can be used as a power supply source outside the vehicle. In this case, for example, the use of commercial power supplies during peak power demand periods can be avoided. If the use of commercial power supplies during peak power demand periods can be avoided, it will help save energy and reduce carbon dioxide emissions. In addition, if the cycle characteristics are excellent, the secondary battery can be used for a long period of time, thereby reducing the use of rare metals such as cobalt.

[0349] This embodiment mode can be implemented in combination with other embodiment modes as appropriate. [Example]

[0350] In this example, a positive electrode active material according to one embodiment of the present invention was produced and the crystal structure of the positive electrode active material after charging was analyzed.

[0351] <Manufacturing of Positive Electrode Active Material> The sample manufactured in this example will be described with reference to the manufacturing method shown in FIG. 4 .

[0352] <Sample 1> exist Figure 4A In step S11, lithium carbonate (Li2CO3) as a lithium (Li) source, tetracobalt trioxide (Co3O4) as a cobalt (Co) source, and nickel hydroxide (Ni(OH)2) as a nickel (Ni) source are prepared and weighed in such a manner that Li:Co:Ni=1:0.8:0.2 (atomic ratio).

[0353] Next, in step S12, the lithium source, the cobalt source, and the nickel source are mixed by a wet process using a ball mill. Dehydrated acetone is used as a solvent, and zirconium oxide balls are used as a grinding medium. With 20mL of dehydrated acetone, zirconium oxide ball A total of 10 g of the lithium source, cobalt source and nickel source were placed in a 45 mL mixing ball mill, the rotation speed of the ball mill was set to 300 rpm (the diameter of the ball mill was 40 mm), and the treatment time was set to 20 hours.

[0354] Next, in step S13, the mixture obtained above is heated at 900°C for 10 hours using a muffle furnace. Dry air is used as the atmosphere, and the flow rate is set to 10 L / min.

[0355] Through the above process, LiCo 0.8 Ni 0.2 The positive electrode active material having a composition of O2 is recorded as Sample 1.

[0356] <Sample 2> exist Figure 4B In step S11 to step S14, the same process as sample 1 was performed to obtain a LiCo 0.8 Ni 0.2 O2 is a positive electrode active material. Figure 4B The source of the additional element A added in step S20 is selected from magnesium and fluorine. Figure 4C In step S21, magnesium fluoride (MgF2) and lithium fluoride (LiF) are used as magnesium (Mg) sources, and lithium fluoride is used as a fluorine source. The weighing is performed so that LiF:MgF2=1:3 (molar ratio).

[0357] Then, in Figure 4C In step S22, a magnesium source (Mg source) and a fluorine source are mixed to obtain an additive element A source.

[0358] Then, in Figure 4B In step S31, MgF2 is weighed so that 0.5 mol% of the transition metal M and LiF is weighed so that 0.17 mol% of the transition metal M is made, and the above MgF2, LiF and LiCo are mixed by dry method. 0.8 Ni 0.2 O2. At this time, stirring is performed at a rotation speed of 150 rpm for 1 hour. This is a more gentle stirring condition than when obtaining source A. Finally, a mixture 903 with a uniform particle size is obtained by screening using a sieve with a mesh size of 300 μm (step S32).

[0359] Next, as step S33, the mixture 903 is heated. The heating conditions are 850°C and 2 hours. During the heating, the crucible containing the mixture 903 is covered with a lid. An oxygen atmosphere is used, and its flow rate is set to 10 L / min. A positive electrode active material containing Mg and F is obtained by heating (step S34). This is recorded as sample 2.

[0360] <Sample 3> In step S20, sample 3 is manufactured. The manufacturing conditions of sample 3 are different from those of sample 2 in that no additional element is added in the former.

[0361] <Sample 4> In step S11, sample 4 is manufactured. The manufacturing conditions of sample 4 are different from those of sample 1 in that: in the former, lithium carbonate (Li2CO3) as a lithium (Li) source, cobalt tetraoxide (Co3O4) as a cobalt (Co) source, and nickel hydroxide (Ni(OH)2) as a nickel (Ni) source are weighed in the manner of Li:Co:Ni=1:0.9:0.1 (atomic ratio).

[0362] <Sample 5> In step S11, sample 5 is manufactured. The manufacturing conditions of sample 5 are different from those of sample 2 in that: in the former, lithium carbonate (Li2CO3) as a lithium (Li) source, cobalt tetraoxide (Co3O4) as a cobalt (Co) source, and nickel hydroxide (Ni(OH)2) as a nickel (Ni) source are weighed in the manner of Li:Co:Ni=1:0.9:0.1 (atomic ratio).

[0363] <Sample 6> In step S11, sample 6 is manufactured. The manufacturing conditions of sample 6 are different from those of sample 1 in that: in the former, lithium carbonate (Li2CO3) as a lithium (Li) source, cobalt tetraoxide (Co3O4) as a cobalt (Co) source, and nickel hydroxide (Ni(OH)2) as a nickel (Ni) source are weighed in the manner of Li:Co:Ni=1:0.95:0.05 (atomic ratio).

[0364] <Sample 11> In step S11, sample 11 is manufactured. The manufacturing conditions of sample 11 are different from those of sample 1 in that: in the former, lithium carbonate (Li2CO3) as a lithium (Li) source, cobalt tetraoxide (Co3O4) as a cobalt (Co) source, and nickel hydroxide (Ni(OH)2) as a nickel (Ni) source are weighed in the manner of Li:Co:Ni=1:0.99:0.01 (atomic ratio).

[0365] <Sample 12> In step S11, sample 12 is manufactured. The manufacturing conditions of sample 12 are different from those of sample 2 in that: in the former, lithium carbonate (Li2CO3) as a lithium (Li) source, cobalt tetraoxide (Co3O4) as a cobalt (Co) source, and nickel hydroxide (Ni(OH)2) as a nickel (Ni) source are weighed in the manner of Li:Co:Ni=1:0.99:0.01 (atomic ratio).

[0366] Table 1 shows the manufacturing conditions of Samples 1 to 6, Sample 11, and Sample 12.

[0367] [Table 1]

[0368] <xrd> After the positive electrode active materials were manufactured and before they were used in half cells, the crystal structures of Samples 1, 4, and 6 were analyzed by XRD.

[0369] In addition, when half cells were assembled using Samples 1 to 6, Sample 11, and Sample 12 and charged at 4.5 V, 4.6 V, or 4.7 V, the crystal structures of the samples were analyzed by XRD.

[0370] The conditions of the half-cell are described below. First, the above-mentioned positive electrode active material is prepared, acetylene black (AB) is prepared as a conductive material, and polyvinylidene fluoride (PVDF) is prepared as a binder, and a slurry is prepared by mixing the positive electrode active material: AB: PVDF = 95:3:2 (weight ratio), and the slurry is applied to the aluminum current collector. NMP is used as a solvent for the slurry.

[0371] After the slurry is applied to the current collector, the solvent is evaporated. Through the above process, a positive electrode is obtained. The active material loading of the positive electrode is 7 mg / cm 2 about.

[0372] As the electrolyte, an electrolyte prepared by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) at a ratio of 3:7 (volume ratio) and adding 2 wt% of vinylene carbonate (VC) as an additive was used, and as the electrolyte contained in the electrolyte, 1 mol / L of lithium hexafluorophosphate (LiPF6) was used. Polypropylene was used as a separator.

[0373] Lithium metal is prepared as a counter electrode, thereby forming a coin-type half-cell including the above-mentioned positive electrode and the like.

[0374] The charging conditions were set as follows: charging voltage was 4.5 V, 4.6 V or 4.7 V, charging method was CCCV (constant current was 68.5 mA / g, upper limit voltage was each voltage, and termination current was 1.37 mA / g), and charging temperature was 25°C.

[0375] Immediately after charging, the charged half-cell was disassembled in an argon atmosphere glove box to remove the positive electrode, and the electrolyte was removed by washing with DMC (dimethyl carbonate). The removed positive electrode was attached to a flat substrate using double-sided tape and placed in an airtight sample holder under an argon atmosphere. The positive electrode active material layer was set along the measurement surface required by the device. XRD measurements were performed at room temperature regardless of the temperature during charging.

[0376] The apparatus and conditions for XRD measurement were set as follows. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: Cu Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 75° or 15° to 70° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm The background and the peak of the CuKα2 line in the obtained XRD pattern were removed by using the analysis software DIFFRAC.EVA.

[0377] Fig.12 XRD patterns of Sample 1, Sample 4, and Sample 6 after the positive electrode active material is produced and before it is used in a half cell (hereinafter also referred to as after synthesis) are shown. FIG. 13A to FIG. 14B Show Fig.15 A portion of the enlarged pattern.

[0378] Fig.15 The XRD patterns of Sample 1 when the charging voltage was set to 4.5 V, 4.6 V, and 4.7 V are shown. FIG. 16A to FIG. 17B Show Fig.15 A portion of the enlarged pattern.

[0379] Fig.18 The XRD patterns of Sample 2 when the charging voltage was set to 4.5 V, 4.6 V, and 4.7 V are shown. FIG. 19A to FIG. 20B Show Fig.18 A portion of the enlarged pattern.

[0380] Fig.21 The XRD patterns of Sample 3 when the charging voltage was set to 4.5 V, 4.6 V, and 4.7 V are shown. FIG. 22A to FIG. 23B Show Fig.21 A portion of the enlarged pattern.

[0381] Fig.24 The XRD patterns of Sample 4 when the charging voltage was set to 4.5 V, 4.6 V, and 4.7 V are shown. FIG. 25A to FIG. 26B Show Fig.24 A portion of the enlarged pattern.

[0382] Fig. 27 The XRD patterns of Sample 5 when the charging voltage was set to 4.5 V, 4.6 V, and 4.7 V are shown. FIG. 28A to FIG. 29B Show Fig. 27 A portion of the enlarged pattern.

[0383] Fig.30 The XRD pattern of Sample 6 when the charging voltage was set to 4.7 V is shown. FIG. 31A to FIG. 32B Show Fig.30 A portion of the enlarged pattern.

[0384] Fig.33 The XRD pattern of Sample 11 when the charging voltage is set to 4.6 V is shown. FIG. 34A to FIG. 35B Show Fig.33 A portion of the enlarged pattern.

[0385] Fig.36 The XRD pattern of Sample 12 when the charging voltage was set to 4.6 V is shown. FIG. 37A to FIG. 38B Show Fig.36 A portion of the enlarged pattern.

[0386] Table 2 shows the angles and intensity ratios of the main peaks appearing in the XRD patterns of Samples 1, 4, and 6 before being used in half-cells, and in the XRD patterns of Samples 1 to 6 at each charging voltage. In Table 2, - (hyphen) indicates a situation where no clear peak is seen. Note that the value of 2θ drifts globally due to the misalignment of the measurement surface when the sample is set in the XRD analysis device. For example, sometimes all the peaks in a certain XRD pattern drift in the same direction by a maximum of about 0.1°. In this case. Use analysis software such as DIFFRAC.TOPAS for correction, and the corrected result can be used.

[0387] [Table 2]

[0388] Regarding the XRD patterns of Samples 1, 4, and 6 after synthesis, and the XRD patterns at each charging voltage of Samples 1 to 6, DIFFRAC.TOPAS was used to analyze the crystal structure of the positive electrode active material. The space groups all belong to R-3m. Table 3 shows the lattice constant, grain size, and unit cell volume. When the Scheele constant k=1, the grain size is calculated using Lvol-1B. In addition, the charging capacity of some samples at various voltages is also shown. In addition, for samples having XRD patterns both after synthesis and in the charging state, the rate of change of the lattice constant of the a-axis Δa, the rate of change of the lattice constant of the c-axis Δc, and the rate of change of the unit cell volume ΔV are also shown. Note that when the value increases after synthesis, the rate of change is expressed as positive, and when the value decreases after synthesis, the rate of change is expressed as negative.

[0389] [Table 3]

[0390] In the unit cell of the synthesized sample 1, the coordinates of cobalt and oxygen are Co (0, 0, 0.5) and O (0, 0, 0.2394).

[0391] In the unit cell of the synthesized sample 4, the coordinates of cobalt and oxygen are Co (0, 0, 0.5) and O (0, 0, 0.238).

[0392] In the unit cell of the synthesized sample 6, the coordinates of cobalt and oxygen are Co (0, 0, 0.5) and O (0, 0, 0.2391).

[0393] from Fig.12 From FIG. 38 , Table 2 and Table 3, it can be seen that the higher the Ni / (Co+Ni), the larger the lattice constants and unit cell volumes of the a-axis and c-axis tend to be, and thus Vegard's law holds true.

[0394] In addition, samples 1 to 6 in which Ni / (Co+Ni) is greater than 0.05 and less than 0.2, for example, show relatively clear peaks in the XRD pattern after charging at 4.6V, so it can be inferred that the above samples have stable crystal structures. On the other hand. Samples 11 and 12 in which Ni / (Co+Ni) is 0.01 have unclear peaks in the XRD pattern after charging at 4.6V, so it can be inferred that their crystal structures are collapsing. Therefore, it can be considered that Ni / (Co+Ni) is preferably greater than 0.01.

[0395] In addition, in sample 6 with Ni / (Co+Ni) of 0.05, an XRD pattern that may be CoO2(O1) was confirmed when charged at 4.7V. The CoO2(O1) structure is formed by the CoO2 layer deviating from LiMO2, so the crystal structure is prone to collapse when the charge and discharge of the structure are repeated, which may have a negative impact on the cycle characteristics. Therefore, it can also be said that Ni / (Co+Ni) is preferably greater than 0.05, and more preferably greater than 0.1.

[0396] In addition, the higher the Ni / (Co+Ni), the smaller the change rate ΔV of the unit cell volume tends to be. This is a desirable property for all-solid-state secondary batteries and the like that have a problem of volume change during charge and discharge.

[0397] On the other hand, the lower the Ni / (Co+Ni), the smaller the change rate Δa of the a-axis lattice constant tends to be, so it is expected that the stability of the crystal structure will be improved. Therefore, Ni / (Co+Ni) is preferably 0.3 or less, and more preferably 0.215 or less. [Explanation of symbols]

[0398] 100: positive electrode active material, 100a: surface layer, 100b: interior, 101: grain boundary, 104: coating< / xrd> < / edx> < / xrd>

Claims

1. A positive electrode active material comprising cobalt, nickel, oxygen and an additive element, in, The ratio of nickel to the total of cobalt and nickel, Ni / (Co+Ni), is greater than or equal to 0.1 and less than or equal to 0.3, The positive electrode active material includes a surface portion and an inner portion, The average detected amount of the added element in the surface layer is higher than the average detected amount of the added element in the interior. Furthermore, the additional element is one or more elements selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

2. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.526±0.1°, 2θ=37.391±0.1°, 2θ=37.628±0.1°, 2θ=39.015±0.1°, 2θ=44.947±0.1°, 2θ=49.029±0.1° and 2θ=58.857±0.1°.

3. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.351±0.1°, 2θ=37.412±0.1°, 2θ=38.974±0.1°, 2θ=44.865±0.1°, 2θ=48.864±0.1° and 2θ=58.621±0.1°.

4. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.7V (vs. Li / Li + ) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.382±0.1°, 2θ=37.391±0.1° and 2θ=44.886±0.1°.

5. A positive electrode active material comprising cobalt, nickel, oxygen and an additive element, in, The added elements are magnesium and fluorine. The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.516±0.1°, 2θ=37.391±0.1°, 2θ=37.586±0.1°, 2θ=38.995±0.1°, 2θ=44.947±0.1°, 2θ=49.039±0.1° and 2θ=58.898±0.1°.

6. A positive electrode active material comprising cobalt, nickel, oxygen and an additive element, in, The added elements are magnesium and fluorine. The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.608±0.1°, 2θ=37.381±0.1°, 2θ=37.792±0.1°, 2θ=39.015±0.1°, 2θ=44.999±0.1°, 2θ=49.101±0.1° and 2θ=58.991±0.1°.

7. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.403±0.1°, 2θ=37.412±0.1°, 2θ=38.985±0.1°, 2θ=44.875±0.1°, 2θ=48.916±0.1° and 2θ=58.662±0.1°.

8. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.608±0.1°, 2θ=37.381±0.1°, 2θ=37.854±0.1°, 2θ=38.995±0.1°, 2θ=45.009±0.1° and 2θ=59.073±0.1°.

9. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.175 and less than 0.

215. Furthermore, the positive electrode active material is charged to 4.7V (vs. Li / Li + ) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.413±0.1°, 2θ=36.774±0.1°, 2θ=37.412±0.1° and 2θ=44.958±0.1°.

10. A positive electrode active material comprising cobalt, nickel, oxygen and an additive element, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.075 and less than 0.

125. The positive electrode active material includes a surface portion and an inner portion, The average detected amount of the added element in the surface layer is higher than the average detected amount of the added element in the interior. Furthermore, the additional element is one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

11. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.075 and less than 0.

125. Furthermore, the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.434±0.1°, 2θ=37.401±0.1°, 2θ=39.005±0.1°, 2θ=44.896±0.1°, 2θ=48.957±0.1° and 2θ=58.744±0.1°.

12. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.075 and less than 0.

125. Furthermore, the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being analyzed by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.567±0.1°, 2θ=37.381±0.1°, 2θ=39.005±0.1° and 2θ=44.978±0.1°.

13. A positive electrode active material comprising cobalt, nickel, oxygen and an additive element, in, The added elements are magnesium and fluorine. The ratio of nickel to the sum of cobalt and nickel is greater than 0.075 and less than 0.

125. Furthermore, the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.537±0.1°, 2θ=37.391±0.1°, 2θ=37.658±0.1°, 2θ=39.005±0.1°, 2θ=44.958±0.1°, 2θ=49.039±0.1° and 2θ=58.898±0.1°.

14. A positive electrode active material comprising cobalt, nickel, oxygen and an additive element, in, The added elements are magnesium and fluorine. The ratio of nickel to the sum of cobalt and nickel is greater than 0.075 and less than 0.

125. Furthermore, the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.547±0.1°, 2θ=37.381±0.1°, 2θ=38.985±0.1°, 2θ=44.978±0.1°, 2θ=49.101±0.1° and 2θ=59.073±0.1°.

15. A positive electrode active material comprising cobalt, nickel, oxygen and an additive element, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.025 and less than 0.

075. The positive electrode active material includes a surface portion and an inner portion, The average detected amount of the added element in the surface layer is higher than the average detected amount of the added element in the interior. Furthermore, the additional element is one or more selected from magnesium, fluorine, calcium, aluminum, silicon, vanadium, copper and gallium.

16. A positive electrode active material comprising cobalt, nickel and oxygen, in, The ratio of nickel to the sum of cobalt and nickel is greater than 0.025 and less than 0.

075. Furthermore, the positive electrode active material is charged to 4.5V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.567±0.1°, 2θ=37.381±0.1°, 2θ=37.710±0.1°, 2θ=38.985±0.1°, 2θ=44.968±0.1°, 2θ=49.070±0.1° and 2θ=58.980±0.1°.

17. A positive electrode active material comprising cobalt, nickel and oxygen, The ratio of nickel to the sum of cobalt and nickel is greater than 0.025 and less than 0.

075. Furthermore, the positive electrode active material is charged to 4.6V (vs. Li / Li + ) in a state of being prepared by X-ray powder diffraction analysis using CuKα1 line, it has diffraction peaks at at least two of 2θ=18.866±0.1°, 2θ=37.319±0.1°, 2θ=38.337±0.1°, 2θ=38.985±0.1°, 2θ=45.143±0.1°, 2θ=49.368±0.1° and 2θ=59.515±0.1°. 18 . A secondary battery comprising the positive electrode active material according to claim 1 .

19. An electronic device comprising the secondary battery according to claim 18.

20. A vehicle comprising the secondary battery according to claim 18.

Citation Information

Patent Citations

  • Method for manufacturing positive electrode active material

    JP2019179758A

  • Positive electrode active material, manufacturing method thereof, and secondary battery

    JP2020140954A

  • Positive electrode active material and method for producing positive electrode active material

    WO2020026078A1